High young's modulus, lithium oxide containing glass

CN122892849APending Publication Date: 2026-10-09CORNING INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580019747.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-02-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

虽然此类解决方案提供了更能抵抗弯曲失效的更坚固的玻璃,但玻璃仍然容易受到动态尖锐接触的影响

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122892849A_ABST
    Figure CN122892849A_ABST
Patent Text Reader

Abstract

A glass comprising 57-68 mol.% SiO2; 9.5-16 mol.% Al2O3; at least 8 mol.% MgO; at least 7 mol.% CaO; at least 7 mol.% Li2O; and less than 4 mol.% Na2O. A glass-based article comprising a compressive stress layer extending from a surface of the glass-based article to a compressive depth; a central tension region; and a composition at a center of the glass-based article comprising the glass. A method for ion exchanging a glass-based substrate, the method comprising ion exchanging the glass-based substrate in a first molten salt bath to form a glass-based article, wherein the glass-based article comprises a compressive stress layer extending from a surface of the glass-based article to a compressive depth, the glass-based article comprises a central tension region, and the glass-based substrate comprises the glass.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 562916, filed March 8, 2024, the contents of which are used as a basis and are incorporated herein by reference in their entirety. Technical Field

[0003] This disclosure generally relates to glasses and glass-based articles having a high Young's modulus, and more specifically, to aluminosilicate glasses and glass-based articles comprising lithium oxide and magnesium oxide and having a high Young's modulus. Such articles are suitable for a variety of applications, including as cover glass and / or housing for electronic devices. Background Technology

[0004] The mobile nature of portable devices (such as smartphones, tablets, portable media players, personal computers, and cameras) makes them particularly vulnerable to accidental drops onto hard surfaces, such as the ground. These devices often incorporate cover glass and / or glass-based housings, which can be damaged upon impact with a hard surface and / or upon experiencing bending stress. In many such devices, the cover glass functions as a display cover and may include touch functionality, meaning that damage to the cover glass can negatively impact the device's usability. Similarly, when the housing is made of glass, damage to the housing can have adverse effects.

[0005] Thin glass is needed for various reasons, such as to reduce material costs and to manufacture devices with a thinner overall profile. However, thinner glass is generally more prone to bending failure and sharp-contact failure.

[0006] For example, glass can be made stronger by ion-exchanging it to introduce a compressive stress layer. While such solutions provide stronger glass that is more resistant to bending failure, the glass remains susceptible to dynamic sharp contact.

[0007] Therefore, there remains a need in the art for glass and glass-based articles with desired properties, including desired mechanical properties such as high Young's modulus. Summary of the Invention

[0008] In various respects, this disclosure relates to a glass comprising:

[0009] 57-68 mol.% SiO2;

[0010] 9.5-16 mol.% Al2O3;

[0011] At least 8 mol.% MgO;

[0012] At least 7 mol.% CaO;

[0013] At least 7 mol.% Li₂O; and

[0014] Less than 4 mol.% Na2O.

[0015] This disclosure also relates in various aspects to a method for ion exchange of a glass substrate, the method comprising:

[0016] The glass substrate is subjected to ion exchange in a first molten salt bath to form a glass-based article.

[0017] The glass substrate includes a compressive stress layer extending from the surface of the glass substrate to a compression depth, the glass substrate includes a central tension region, and the glass substrate comprises the glass composition disclosed herein.

[0018] In all respects, this disclosure relates to a glass-based article comprising:

[0019] A compressive stress layer, the compressive stress layer extending from the surface of the glass substrate to a certain compression depth;

[0020] Central tension region; and

[0021] The composition located at the center of the glass-based article, the composition comprising:

[0022] 57-68 mol.% SiO2;

[0023] 9.5-16 mol.% Al2O3;

[0024] At least 8 mol.% MgO;

[0025] At least 7 mol.% CaO;

[0026] At least 7 mol.% Li₂O; and

[0027] Less than 4 mol.% Na2O.

[0028] In various respects, this disclosure also relates to a consumer electronics product comprising:

[0029] The housing has a front surface, a rear surface, and side surfaces;

[0030] Electrical components, at least partially disposed within the housing, the electrical components including at least a controller, a memory, and a display, the display being disposed on or adjacent to the front surface of the housing; and

[0031] A cover plate, which is disposed above the display;

[0032] At least a portion of at least one of the housing and the cover substrate comprises the glass-based article disclosed herein.

[0033] Other features and advantages of this disclosure will be set forth in the following detailed description, and some of these features and advantages will be apparent to those skilled in the art from the description or will be recognized by practice of the various aspects described herein, including the following detailed description, the claims, and the drawings.

[0034] It should be understood that the foregoing general description and the following detailed description are merely exemplary and intended to provide an overview or framework for understanding the nature and characteristics of this disclosure and the claims. The accompanying drawings are included to provide a further understanding of this disclosure and are incorporated in and form a part of this specification. The drawings illustrate various aspects of this disclosure and, together with the description, serve to explain the principles and operation of those aspects. Attached Figure Description

[0035] The following detailed description can be further understood when read in conjunction with the accompanying drawings. Where possible, the same reference numerals will be used throughout the drawings to refer to the same or similar parts. It should be understood that the drawings are not drawn to scale, and the size of each depicted part or the relative size of one part to another is not intended to be limiting.

[0036] Figure 1 A cross-section of a glass-based article having a region of compressive stress is schematically depicted according to the aspects described and disclosed herein.

[0037] Figure 2A This is a plan view of an exemplary electronic device incorporated in any of the glass-based articles disclosed herein.

[0038] Figure 2B yes Figure 2A A perspective view of an exemplary electronic device.

[0039] Figure 3 This is an example of stress distribution in ion-exchanged glass products.

[0040] Figure 4 This is an example of stress distribution in ion-exchanged glass products.

[0041] Figure 5 This is an example of stress distribution in ion-exchanged glass products compared to other ion-exchanged glass products.

[0042] Figure 6This is an example of stress distribution in ion-exchanged glass products compared to other ion-exchanged glass products.

[0043] Figure 7 This is an example of stress distribution in ion-exchanged glass products compared to other ion-exchanged glass products. Detailed Implementation

[0044] In the following description, whenever a group is described as comprising at least one of groups containing elements and combinations thereof, it should be understood that the group may contain any number of those stated elements individually or in combination with each other, substantially constitute or consist of them. Similarly, whenever a group is described as consisting of at least one of groups containing elements or combinations thereof, it should be understood that the group may consist of any number of those stated elements individually or in combination with each other.

[0045] Where a range of numerical values ​​containing upper and lower limits is stated herein, unless otherwise stated in specific circumstances, the range is intended to include its endpoints, as well as all integers and fractions within the range. Furthermore, when a quantity, concentration, or other value or parameter is given in the form of a range, one or more ranges, or a list of upper and lower limits, this should be understood to specifically disclose all ranges formed by any pair of any upper limit or value and any lower limit or value, regardless of whether such pairs are disclosed individually.

[0046] When the term “about” is used to describe a range of values ​​or endpoints, this disclosure should be understood to include the specific values ​​or endpoints mentioned. As used herein, the term “about” means that a quantity, size, formulation, parameter, and other quantity and characteristic is not and does not need to be precise, but may be approximate and / or larger or smaller as required, reflecting tolerances, conversion factors, rounding, measurement errors, and other factors known to those skilled in the art. It should be noted that the term “substantially” can be used herein to indicate the degree of inherent uncertainty attributable to any quantitative comparison, value, measurement result, or other representation. These terms are also used herein to indicate the extent to which a quantitative representation may differ from the stated reference without causing a fundamental change in the function of the subject matter of interest. Therefore, for example, a glass that is “substantially free” of any particular component (e.g., Al2O3, MgO, or any other component) is a glass in which said component is not actively added or added in batches to the glass but may be present as a contaminant in small amounts (e.g., less than 1000 ppm, 500 ppm, 400 ppm, 300 ppm, 200 ppm, or 100 ppm), or if it is actively added or added in batches, it is present in amounts less than 1 wt.% (e.g., or may be specified as less than 0.5 wt.%, 0.1 wt.%, or 0.05 wt.%) based on the total amount of the glass (in molar or mass for ppm and in mass for wt.%).

[0047] Typically, lithium aluminosilicate glasses possess excellent ion exchange capacity, and their high strength and toughness are achieved through chemical strengthening processes. Replacing Al₂O₃ with Al₂O₃ in the silicate glass network increases the interdiffusion of monovalent cations during ion exchange, and by chemical strengthening in a molten salt bath (e.g., KNO₃ or NaNO₃), glasses with a variety of desired properties can be obtained, including high strength, high toughness, and high resistance to dent cracking. The stress distribution achieved through chemical strengthening can be varied in shape, thereby improving the drop performance, strength, toughness, and other properties of glass-based articles.

[0048] In some respects, this paper provides lithium-containing aluminosilicate glasses with high Young's modulus. The compositions disclosed herein are unique and represent a balance of constituent components, resulting in high Young's modulus and higher compressive stress after ion exchange than other lithium-containing aluminosilicates. Greater center tension (CT), depth of compression (DOC), and high compressive stress (CS) can be achieved through different ion exchange processes.

[0049] High Young's modulus glasses and glass-ceramic materials are expected to be used in a wide range of applications, from handheld devices to memory disks to optical fibers. A high Young's modulus can lead to an increase in the glass's brittleness limit and often also results in high fracture toughness values. For applications requiring or involving hard coatings mounted on a glass substrate, a high Young's modulus glass substrate is advantageous because the increased substrate modulus generally reduces the bending radius the coating can withstand. This reduces the likelihood of the coating cracking and delaminating with the substrate.

[0050] For glass, the inclusion of large amounts of high field strength oxides, such as MgO, Y₂O₃, and La₂O₃, can typically result in high Young's modulus. However, the difficulty with including large amounts of these elements lies in their generally high refractory properties, making it easy for the liquidus temperature to become too high for manufacturing. Surprisingly, this paper finds that careful balancing of the composition results in ion-exchangeable, Li₂O-containing aluminosilicate compositions with high Young's modulus values ​​while still maintaining desired processability parameters. In this paper, the high Young's modulus values ​​are obtained with high MgO content, such as at least 8 mol.% and in some respects up to 30 mol% or possibly more. Many published glasses have liquidus viscosity values ​​(e.g., >500 P) compatible with rolling capabilities.

[0051] As used herein, the term "ion-exchangeable" refers to a glass composition that allows for chemical strengthening through ion exchange. For example, a glass with a suitable structure and containing lithium can undergo ion exchange in a molten salt bath containing sodium and / or potassium, thereby replacing a portion of the lithium with sodium and / or potassium. Similarly, a glass with a suitable structure and containing sodium can undergo ion exchange in a molten salt bath containing potassium, thereby replacing a portion of the sodium with potassium. As is known in the art, replacing smaller alkali ions in a glass with larger alkali ions generates compressive stress in the glass, thereby strengthening it. A "suitable structure" in a glass refers to a structure that allows ion exchange to occur, thereby generating compressive stress in the glass and achieving the corresponding strengthening.

[0052] In this document, unless otherwise stated, glass compositions are expressed in mol.% amounts based on oxides containing specific components. Any component having more than one oxidation state may be present in the glass composition in any oxidation state. However, unless otherwise stated, the concentration of such components is expressed in the oxide in which such component is in its lowest oxidation state.

[0053] As used herein, “fragility limit” refers to the central tension or stored strain energy above which a glass-based article exhibits brittle behavior. “Fragility” or “brittle behavior” refers to specific fracture behavior of a material upon impact or damage. As used herein, a glass-based article is considered non-fragile as a result of a fragility test when it exhibits no branching within the test area. As used herein, a branch originating at the point of impact and extending into the test area at any point is considered within the test area. Fragments, bifurcations, and branches are counted based on any 25 mm by 25 mm square centered on the point of impact. Therefore, if a glass-based article does not exhibit any branching within any 25 mm by 25 mm square centered on the point of impact, it is considered non-fragile, where breakage is caused according to the procedure described below. If a glass-based article exhibits five or more branches within any 25 mm by 25 mm square centered on the point of impact, it is considered “critically fragile” or close to the fragility limit. A glass-based article is considered “fragile” if it exhibits more than five branches within any 25 mm by 25 mm square centered on the impact point. In the fragility test, an impact probe contacts the multiphase glass, and in successive contact iterations, the depth to which the impact probe penetrates the multiphase glass increases. This gradual increase in probe depth allows the crack induced by the impact probe to reach the tension zone, while preventing the application of excessive external forces that would hinder accurate determination of the glass-based article's fragility behavior. In all respects, the depth of the impact probe in the multiphase glass may increase by approximately 5 µm in each iteration, with the impact probe being removed from contact with the glass-based article between each iteration. The test area is any 25 mm by 25 mm square centered on the impact point. While coatings, adhesive layers, etc., can be used in conjunction with the multiphase glass described herein, such external constraints are not used in determining the fragility or fragility behavior of the multiphase glass. In all respects, prior to the fragility test, a film that does not affect the fracture behavior of the multiphase glass may be applied to the multiphase glass to prevent fragments from ejecting from the multiphase glass.

[0054] As used herein, the term "softening point" refers to a glass composition with a viscosity of 1 × 10⁻⁶. 7.6 Temperature at poise. Softening point was determined using the parallel plate viscosity method according to ASTM C1351M-96 (2012).

[0055] As used herein, the term "annealing point" refers to a glass composition with a viscosity of 1 × 10⁻⁶. 13 Temperature at the time of berthing.

[0056] As used herein, the term "strain point" refers to a glass composition with a viscosity of 1 × 10⁻⁶.14.68 Temperature at the time of berthing.

[0057] As used herein, “glass substrate” refers to a glass sheet that has not undergone ion exchange. Similarly, “glass article” refers to a glass sheet formed by ion exchange and by performing an ion exchange process on a glass substrate. Therefore, “glass substrate” and “glass article” are defined and include glass substrates and glass articles, as well as substrates and articles made wholly or partially of glass, such as glass substrates including surface coatings. Although for convenience, reference may generally be made to glass substrates and glass articles herein, the description of glass substrates and glass articles should be understood to apply equally to glass substrates and glass articles.

[0058] The compositions described herein are chosen to achieve high Young's modulus values ​​and, in some respects, high fracture toughness values, while in either case maintaining the desired degree of manufacturability.

[0059] In some aspects, the glass compositions disclosed herein comprise one or more of SiO2, Al2O3, MgO, CaO, and Li2O.

[0060] In some aspects, the glass composition comprises 57-68 mol.% SiO2; 9.5-16 mol.% Al2O3; at least 8 mol.% MgO; at least 7 mol.% CaO; at least 7 mol.% Li2O; and less than 4 mol.% Na2O. In some aspects, the glass composition comprises 58-64 mol.% SiO2; 9.5-14 mol.% Al2O3; 8-15 mol.% MgO; 7-15 mol.% CaO; 7-15 mol.% Li2O; and less than 1 mol.% Na2O.

[0061] In some aspects of the glass compositions described herein, SiO2 is the largest component, and therefore, it is the main component of the glass network formed by the glass composition. Pure SiO2 has a relatively low coefficient of thermal expansion (CTE). However, pure SiO2 has a high melting point. Therefore, if the concentration of SiO2 in the glass composition is too high, the formability of the glass composition may be reduced, as a higher concentration of SiO2 increases the difficulty of melting the glass, thus adversely affecting its formability. Additionally, including excessive SiO2 in the glass composition reduces the glass's ability to generate compressive stress through ion exchange. If the concentration of SiO2 in the glass composition is too low, the chemical durability of the glass may be reduced, and the glass may be susceptible to surface damage during post-forming processing. In some aspects, the glass composition typically contains SiO2 in amounts (mol.%) of at least 50, at least 53, at least 55, at least 56, at least 57, at least 58, at least 59, at least 60, at least 61, at least 62, at least 63, at least 64, at least 65, at least 66, at least 67, at least 68, at least 69, 74 or less, 72 or less, 70 or less, 69 or less, 68 or less, 67 or less, 66 or less, 65 or less, 64 or less, 63 or less, 62 or less, 61 or less, 60 or less, 59 or less, 58 or less, 57 or less, 56 or less, 55 or less, 53 or less, 51 or less, or any range thereof. For example, in some aspects, the glass composition typically contains amounts (mol.%) of 50-74, 55-70, 55-68, 55-66, 55-64, 55-62, 55-60, 55-58, 55-57, 57-70, 57-68, 57-66, 57-64, 57-62, 57-60, 57-59, 57-58, 58-70, 58-6 8. 58-66, 58-64, 58-63, 58-62, 58-60, 58-59, 59-70, 59-68, 59-66, 59-64, 59-62, 59-60, 62-70, 62-68, 62-66, 62-64, 64-70, 64-68, 64-66, 66-70, 66-68 or 68-70 SiO2. Specifically, in some aspects, the glass composition contains 50-74, 55-70, 58-64, 58-63 or 57-68 mol.% SiO2.

[0062] In some aspects, the glass composition includes Al₂O₃. In some aspects, similar to SiO₂, Al₂O₃ can act as a glass network forging. In some aspects, Al₂O₃, due to its tetrahedral coordination, can increase the liquidus viscosity of the glass melt formed from the glass composition, thereby reducing the formability of the glass composition when the amount of Al₂O₃ is too high. However, when the concentration of Al₂O₃ in the glass composition is in equilibrium with the concentrations of SiO₂ and alkali metal oxides, Al₂O₃ can lower the liquidus temperature of the glass melt, thereby increasing the liquidus viscosity and improving the compatibility of the glass composition with certain forming processes. An increase in the Al₂O₃ content in the glass composition relative to the total content of alkali metal oxides and alkaline earth metal oxides generally improves the durability of the glass. When the concentration of alkali metal oxides (R₂O) is close to or greater than the amount of Al₂O₃ in the glass composition, almost all or all of the aluminum in the glass exists in a tetrahedral coordination state, where alkali metal ions act as charge compensators. This charge balance allows for high diffusivity of alkali ions, thereby increasing the ion exchange rate. In some aspects, the inclusion of Al2O3 in the glass composition achieves the high fracture toughness values ​​described herein. In some aspects, the glass composition contains Al2O3 in an amount (mol.%) of at least 5, at least 7, at least 9, at least 9.5, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, 20 or less, 19 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9.5 or less, or any range thereof.For example, in some aspects, the glass composition comprises 5-20, 5-19, 5-17, 5-16, 5-15, 5-14, 5-13, 5-12, 5-11, 5-10, 5-9.5, 5-9, 6-20, 6-19, 6-17, 6-16, 6-15, 6-14, 6-13, 6-12, 6-11, 6-10, 6-9.5, 6- 9, 7-20, 7-19, 7-17, 7-16, 7-15, 7-14, 7-13, 7-12, 7-11, 7-10, 7-9.5, 7-9, 9-20, 9-19, 9-17, 9-16, 9-15, 9-14, 9-13, 9-12, 9-11, 9-10, 9-9.5, 9.5-20, 9.5-19, 9.5 -17, 9.5-16, 9.5-15, 9.5-14, 9.5-13, 9.5-12, 9.5-11, 9.5-10, 10-20, 10-17, 10-16, 10-15, 10-14, 10-13, 10-12, 10-11, 11-20, 11-17, 11-16, 11-15, 11-14, 11- 13, 11-12, 12-20, 12-17, 12-16, 12-15, 12-14, 12-13, 13-20, 13-17, 13-16, 13-15, 13-14, 14-20, 14-17, 14-16, 14-15, 15-20, 15-17, 15-16, 16-17, 16-20, or 17-20. Specifically, in some aspects, the glass composition contains 5-20, 9.5-16, 9.5-14, 9.5-13, or 10-14% Al2O3. In some aspects, the glass composition contains no or substantially no Al2O3.

[0063] In some respects, the glass compositions described herein include MgO. In some respects, MgO can reduce the liquidus viscosity of the glass and improve melting behavior, which enhances the glass's formability and manufacturability. In some respects, including MgO in the glass composition can also improve the strain point and Young's modulus of the glass composition. However, if too much MgO is added to the glass composition, the liquidus viscosity may become too low to be compatible with the desired forming techniques. Adding too much MgO can also increase the density and CTE of the glass composition to undesirable levels and reduce the mobility of alkali ions in the glass, thereby reducing the effectiveness of ion exchange treatment. Due to the high field strength of MgO, including MgO in the glass composition also contributes to achieving the high fracture toughness values ​​described herein. In some aspects, the glass composition contains (mol.%) at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 12, at least 14, at least 15, at least 16, at least 18, at least 20, at least 22, at least 24, at least 26, at least 28, at least 30, 30 or less, 28 or less, 26 or less, 24 or less, 22 or less, 20 or less, 18 or less, 16 or less, 15 or less, 14 or less, 12 or less, 10 or less, 9 or less, 8 or less, or any range of MgO formed therefrom. For example, in some aspects, the glass composition contains (mol.%) amounts of 5-30, 7-30, 7-28, 7-24, 7-20, 7-18, 7-14, 7-10, 7-8, 8-30, 8-28, 8-26, 8-24, 8-22, 8-20, 8-18, 8-16, 8-15, 8-14, 8-12, 8-10, 9-30, 9-28, 9-24, 9-20, 9-18, 9-16, 9-14, 9-10, 10-30, 10-24, 10-20, 10-16, 10-12, 12-30, 1 MgO in the following quantities: 2-26, 12-22, 12-20, 12-18, 12-14, 14-30, 14-26, 14-22, 14-18, 14-16, 16-30, 16-26, 16-22, 16-20, 16-18, 18-30, 18-28, 18-24, 18-20, 20-30, 20-28, 20-26, 20-24, 20-22, 22-30, 22-28, 22-26, 22-24, 24-30, 24-28, 24-26, 26-30, 26-28, or 28-30. In some aspects, the glass composition contains no or substantially no MgO. Specifically, in some aspects, the glass composition contains at least 8, 8-30, 8-15 or 8-14 MgO in amounts (mol.%).

[0064] In some respects, the glass compositions described herein may include CaO. In some respects, CaO can reduce the liquidus viscosity of the glass, which can enhance formability, strain point, and Young's modulus. However, due to the reduced alkali ion mobility, if too much CaO is added to the glass composition, the density and CTE of the glass composition may increase to undesirable levels, and the ion exchangeability of the glass may also be undesirably hindered. In some aspects, the glass composition contains (mol.%) at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, 20 or less, 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, or any range of CaO formed therefrom. For example, in some aspects, the glass composition content (mol.%) is 5-20, 5-19, 5-18, 5-17, 5-16, 5-15, 5-14, 5-13, 5-12, 5-11, 5-10, 5-9.5, 5-9, 5-8, 5-7, 5-6, 6-20, 6-19, 6-18, 6-15, 6-14, 6-13, 6-12, 6-11, 6-10, 6-9.5, 6-9, 6-8, 6-7, 7-20, 7-15, 7-14, 7-13, 7-12, 7-11, 7-10, 7-9.5, 7-9, 7-8, 8-20, 8-15, 8-14, 8-13, 8-12, 8-11, 8-10 8-9.5, 8-9, 9-20, 9-15, 9-14, 9-13, 9-12, 9-11, 9-10, 9-9.5, 9.5-20, 9.5-15, 9.5-14, 9.5-13, 9.5-12, 9.5-11, 9.5-10, 10-20, 10-15, 10-14, 10-13 The glass composition contains 10-12, 10-11, 11-20, 11-15, 11-14, 11-13, 11-12, 12-20, 12-15, 12-14, 12-13, 13-20, 13-15, 13-14, 14-20, 14-17, 14-15, 15-20, 15-17, or 17-20% CaO. In some aspects, the glass composition is substantially free of or contains no CaO. Specifically, in some aspects, the glass composition contains at least 7, 7-20, 7-15, or 8-13% CaO.

[0065] In some aspects, the glass composition includes Li₂O. In some aspects, the inclusion of Li₂O in the glass composition allows for better control of the ion exchange process and further reduces the softening point, liquidus temperature, and melting temperature of the glass, thereby improving the manufacturability of the glass. The presence of Li₂O in the glass composition also promotes the formation of a parabolic stress distribution. Li₂O in the glass composition can also achieve high fracture toughness values. Including too much Li₂O in the glass composition increases the coefficient of thermal expansion and reduces the chemical durability of the glass. In some aspects, if the glass composition contains insufficient Li₂O, the ion exchange capacity of the glass may be undesirably reduced, and the desired stress distribution may not be achieved. In some aspects, the glass composition contains (mol.%) at least 2, at least 3, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, 20 or less, 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, or any range of Li2O formed therefrom. For example, in some aspects, the glass composition contains (mol.%) 2-20, 5-20, 5-19, 5-18, 5-17, 5-16, 5-15, 5-14, 5-13, 5-12, 5-11, 5-10, 5-9, 5-8, 5-7, 5-6, 6-20, 6-19, 6-18, 6-15, 6-14, 6-13, 6-12, 6-11, 6-10, 6-9, 6-8, 6-7, 7-20, 7-15, 7-14, 7-13, 7-12, 7-11, 7-10, 7-9, 7-8, 8-20, 8-15, 8 -14, 8-13, 8-12, 8-11, 8-10, 8-9, 9-20, 9-15, 9-14, 9-13, 9-12, 9-11, 9-10, 10-20, 10-15, 10-14, 10-13, 10-12, 10-11, 11-20, 11-15, 11-14, 11-13, 11-12, 12-20, 12-15, 12-14, 12-13, 13-20, 13-15, 13-14, 14-20, 14-17, 14-15, 15-20, 15-17 or 17-20 Li2O. Specifically, in some aspects, the glass composition contains at least 7, 7-20, 7-15, 8-13, 8-12 or 9-11 mol.% of Li2O.In some respects, the glass composition is essentially free of or contains no Li2O.

[0066] In some aspects, the glass compositions described herein include Na₂O. In some aspects, Na₂O contributes to the ion exchangeability of the glass composition and improves its formability, thereby improving its manufacturability. However, if too much Na₂O is added to the glass composition, the CTE may be too low. Additionally, if the amount of Na₂O included in the glass relative to Li₂O is excessive, it may reduce the glass's ability to achieve deep compression during ion exchange. In some aspects, the glass composition contains Na₂O in an amount (mol.%) of at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, or any range thereof. For example, in some aspects, the glass composition content (mol.%) is 0-10, 0-9, 0-8, 0-7, 0-6, 0-5, 0-4, 0-3, 0-2, 0-1, >0-10, >0-9, >0-8, >0-7, >0-6, >0-5, >0-4, >0-3, >0-2, >0-1, 1-10, 1-9, 1-8, 1-7, 1-6, 1-5, 1-4, 1-3, 1-2, 2 -10, 2-9, 2-8, 2-7, 2-6, 2-5, 2-4, 2-3, 3-10, 3-9, 3-8, 3-7, 3-6, 3-5, 3-4, 4-10, 4-9, 4-8, 4-7, 4-6, 4-5, 5-10, 5-9, 5-8, 5-7, 5-6, 6-10, 6-9, 6-8, 6-7, 7-10, 7-9, 7-8, 8-10, 8-9, or 9-10 Na₂O. In some aspects, the glass composition contains (mol.%) 4 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.5 or less, 0.1 or less, 0.05 or less, or 0.01 or less Na₂O. In some respects, the glass composition is essentially free of or contains no Na2O.

[0067] In some aspects, the glass composition may include one or more clarifying agents. In some aspects, the clarifying agent may include, for example, SnO2. In some aspects, SnO2 may be present in the glass composition in amounts (mol.%) of at least 0.01, at least 0.05, at least 0.1, at least 0.15, at least 0.2, at least 0.25, at least 0.3, at least 0.4, at least 0.6, at least 0.8, 1 or less, 0.8 or less, 0.6 or less, 0.4 or less, 0.3 or less, 0.25 or less, 0.2 or less, 0.15 or less, 0.1 or less, 0.05 or less, 0.01 or less, or any range thereof. For example, in some aspects, the glass composition may contain amounts (mol.%) of 0-1, 0-0.8, 0-0.6, 0-0.4, 0-0.3, 0-0.2, 0-0.1, 0-0.05, >0-1, >0-0.8, >0-0.6, >0-0.4, >0-0.3, >0-0.2, >0-0.1, >0-0.05, 0.05-1, 0.05-0.8, 0.05-0.6, 0.05-0.4, 0.05-0.3, 0.05-0.2, 0.05-0.1, 0.1-1, 0.1-0.8, 0.1-0.6, 0.1-0.4, 0.1-0.3, 0.1-0.25, 0.1- SnO2 in the following concentrations: 0.2, 0.1-0.15, 0.15-1, 0.15-0.8, 0.15-0.6, 0.15-0.4, 0.15-0.3, 0.15-0.25, 0.15-0.2, 0.2-1, 0.2-0.8, 0.2-0.6, 0.2-0.4, 0.2-0.3, 0.2-0.25, 0.25-1, 0.25-0.8, 0.25-0.6, 0.25-0.4, 0.25-0.3, 0.3-1, 0.3-0.8, 0.3-0.6, 0.3-0.4, 0.4-1, 0.4-0.8, 0.4-0.6, 0.6-1, 0.6-0.8, or 0.8-1. Specifically, in some aspects, the glass composition may contain SnO2 in an amount (mol.%) of 0-1, 0-0.5, >0-1, >0-0.2, or >0-0.1%. In some aspects, the glass composition may be substantially free of or contain no SnO2. In some aspects, the glass composition may be free of or substantially free of one or both of arsenic and antimony.

[0068] In some aspects, the glass composition comprises R2O / Al2O3 in any suitable ratio, wherein the amounts of R2O and Al2O3 are expressed in mol.% and R2O is the total amount of Li2O, Na2O, K2O, Rb2O, and Cs2O in the glass composition. In some aspects, the glass composition comprises R2O / Al2O3 in ratios of at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1, at least 1.1, at least 1.2, at least 1.3, at least 1.4, at least 1.5, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, or any range thereof. For example, in some aspects, the glass composition comprises in ratios of 0.4-1.6, 0.4-1.5, 0.4-1.4, 0.4-1.2, 0.4-1, 0.4-0.8, 0.4-0.6, 0.4-0.5, 0.5-1.6, 0.5-1.5, 0.5-1.4, 0.5-1.2, 0.5-1, 0.5-0.8, 0.5-0.6, 0.6-1.6, 0.6-1.5, 0.6-1.4, 0.6-1.2, 0.6-1, 0.6-0.8, and 0.6. The glass composition comprises R2O / Al2O3 in ratios of -0.7, 0.7-1.6, 0.7-1.5, 0.7-1.2, 0.7-1.1, 0.7-0.9, 0.9-1.6, 0.9-1.5, 0.9-1.1, 0.9-1, 1-1.6, 1-1.5, 1-1.4, 1-1.3, 1-1.2, 1-1.1, 1.1-1.6, 1.1-1.5, 1.1-1.4, 1.1-1.3, 1.1-1.2, 1.2-1.6, 1.2-1.4, or 1.4-1.6. Specifically, in some aspects, the glass composition comprises R2O / Al2O3 in ratios of 0.5-1.5, 0.6-1.3, or 0.7-1.2.

[0069] In some aspects, the glass composition comprises RO / Al2O3 in any suitable ratio, wherein the amounts of RO and Al2O3 are expressed in mol.% and RO is the total amount of MgO, CaO, SrO, and BaO in the glass composition. In some aspects, the glass composition comprises RO / Al2O3 in ratios of at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9, at least 2, at least 2.1, at least 2.2, at least 2.3, at least 2.4, 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, 2 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, or any range thereof. For example, in some aspects, RO / Al2O3 is 1.2-2.5, 1.2-2.4, 1.2-2.2, 1.2-2, 1.2-1.8, 1.2-1.6, 1.2-1.4, 1.4-2.5, 1.4-2.4, 1.4-2.2, 1.4-2, 1.4-1.8, 1.4-1.6, 1.6-2.5, 1.6-2.4, 1.6-2.2, 1.6-2, 1.6-1.8, 1.8-2.5, 1.8-2.4, 1.8-2.2, 1.8-2, 2-2.5, 2-2.4, 2-2.2, 2.2-2.5, 2.2-2.4, or 2.4-2.5. Specifically, in some aspects, the glass composition comprises RO / Al2O3 in a ratio of at least 1.4, 1.2-2.5, 1.4-2.3 or 1.4-2.1.

[0070] In some aspects, the glass composition contains (RO + R2O) / Al2O3 in a suitable ratio, where the amounts of RO, R2O, and Al2O3 are expressed in mol.%, RO is the total amount of MgO, CaO, SrO, and BaO in the glass composition, and R2O is the total amount of Li2O, Na2O, K2O, Rb2O, and Cs2O in the glass composition. Without being bound by theory, the (RO + R2O) / Al2O3 ratio is considered an important indicator of glass modifiers, as RO and R2O have a charge-compensating effect on aluminum in the glass. In this regard, to make Al... 3+ Replacing Si in glass structures 4+ As a glass-forming agent, another type needs to be added to the system. 1+Charge balances charge. Although ions in R2O are generally more mobile than those in RO, RO can still provide charge compensation. An appropriate (RO + R2O) / Al2O3 ratio indicates the degree of charge compensation in the glass, and a higher ratio generally results in less modifier locked in the glass network, which may make it easier for Li2O to diffuse out of the glass during ion exchange. In some aspects, the glass composition comprises (RO + R2O) / Al2O3 in ratios of at least 2, at least 2.1, at least 2.2, at least 2.3, at least 2.4, at least 2.5, at least 2.6, at least 2.7, at least 2.8, at least 2.9, at least 3, at least 3.1, at least 3.2, at least 3.3, at least 3.4, at least 3.5, 3.5 or less, 3.4 or less, 3.3 or less, 3.2 or less, 3.1 or less, 3 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, or any range thereof. For example, in some aspects, (RO + R2O / Al2O3 ratios are 2-3.5, 2-3.4, 2-3.2, 2-3, 2-2.8, 2-2.6, 2-2.5, 2-2.4, 2-2.3, 2-2.2, 2-2.1, 2.1-3.5, 2.1-3.4, 2.1-3.2, 2.1-3, 2.1-2.8, 2.1-2.6, 2.1- 2.5, 2.1-2.4, 2.1-2.3, 2.1-2.2, 2.2-3.5, 2.2-3.4, 2.2-3, 2.2-2.8, 2.2-2.6, 2.2-2.5, 2.2-2.4, 2.2-2.3, 2.3-3.5, 2.3-3, 2.3-2.8, 2.3-2.5, 2.3-2. 4, 2.4-3.5, 2.4-3.4, 2.4-3.2, 2.4-3, 2.4-2.8, 2.4-2.5, 2.5-3.5, 2.5-3.2, 2.5-3, 2.5-2.9, 2.5-2.7, 2.5-2.6, 2.6-3.5, 2.6-3.2, 2.6-3, 2.6-2.8, 2 0.6-2.7, 2.7-33.5, 2.7-3.4, 2.7-3.2, 2.7-3, 2.7-2.8, 2.8-3.5, 2.8-3.4, 2.8-3.2, 2.8-3, 3-3.5, 3-3.4, 3-3.2, 3.2-3.5, 3.2-3.4, 3.2-3.3, or 3.3-3.5. In some aspects, the glass composition comprises (RO + R2O) / Al2O3 in a ratio of at least 2, 2-3.5, 2-3.2, or 2.1-3.1.

[0071] In some respects, the glass contains no or substantially no at least one of ZrO2, Y2O3, La2O3, Na2O, K2O, P2O5, SrO and B2O3.

[0072] The liquidus viscosity of the glass compositions described herein is compatible with manufacturing processes particularly suitable for forming thin glass sheets. For example, the glass compositions are compatible with conventional forming methods such as float, rolling, or pressing processes. The glass substrate aspect can be described as fusible-formable (i.e., formable using a fusion drawing process). The fusion process uses a drawing groove having channels for receiving molten glass feedstock. The channels have weirs that open at the top along the length of the channel on both sides. When the channel is filled with molten material, the molten glass overflows the weirs. Due to gravity, the molten glass flows down the outer surfaces of the drawing groove as two flowing glass films. These outer surfaces of the drawing groove extend downwards and inwards, causing them to fuse at the lower edge of the drawing groove. The two flowing glass films fuse at this edge, forming a single flowing glass substrate article. The fusion of the glass films creates a fusion line within the glass substrate, and this fusion line allows for the identification of fused glass substrates without further knowledge of the manufacturing history. The advantage offered by fusion drawing is that, because the two glass films flowing through the channel are fused together, the outer surface of the resulting glass substrate will not come into contact with any part of the equipment. Therefore, such contact will not affect the surface properties of the fusion-drawn glass substrate.

[0073] The glass compositions described herein can be selected to have a liquidus viscosity compatible with fusion drawing processes. Therefore, the glass compositions described herein are compatible with existing forming methods, thereby improving the manufacturability of glass matrix articles formed from the glass compositions. As used herein, the term "liquidus viscosity" refers to the viscosity of molten glass at its liquidus temperature, where the liquidus temperature is the temperature at which crystals first appear when the molten glass is cooled from its melting temperature, or the temperature at which the last crystals melt when the temperature is increased from room temperature. Unless otherwise stated, the liquidus viscosity values ​​disclosed in this application are determined by the following method. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015), entitled "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method". Next, the viscosity of the glass at its liquidus temperature is measured according to ASTM C965-96 (2012), entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point". Unless otherwise specified, the liquidus viscosity and temperature of the glass composition or article are measured before any ion exchange process or any other strengthening process is performed. Specifically, the liquidus viscosity and temperature of the glass composition or article are measured before the composition or article is exposed to an ion exchange medium, such as before immersion in an ion exchange medium like a molten salt bath.

[0074] In some aspects, the glass compositions disclosed herein have any suitable liquidus temperature. For example, in some aspects, the liquidus temperature (°C) is at least 1000, at least 1050, at least 1100, at least 1150, at least 1200, at least 1250, at least 1300, 1300 or lower, 1250 or lower, 1200 or lower, 1150 or lower, 1100 or lower, 1050 or lower, 1000 or lower, or any range thereof. For example, in some aspects, the liquidus temperature (°C) of the glass composition is 1000-1300, 1000-1250, 1000-1200, 1000-1150, 1000-1100, 1000-1050, 1050-1300, 1050-1250, 1050-1200, 1050-1150, 1050-1100, 1100-1300, 1100-1250, 1100-1200, 1100-1150, 1150-1300, 1150-1250, 1150-1200, 1200-1300, 1200-1250, or 1250-1300.

[0075] In some aspects, the glass compositions disclosed herein have any suitable liquidus viscosity. For example, in some aspects, the liquidus viscosity (poise) is at least 800, at least 900, at least 1000, at least 1100, at least 1200, at least 1300, at least 1400, at least 1500, at least 1600, at least 1700, at least 1800, 1900 or less, 1800 or less, 1700 or less, 1600 or less, 1500 or less, 1400 or less, 1300 or less, 1200 or less, 1100 or less, 1000 or less, 900 or less, or any range thereof. For example, in some aspects, the liquidus viscosity (poise) of the glass composition is 800-1900, 800-1800, 800-1600, 800-1400, 800-1200, 800-1000, 800-900, 900-1900, 900-1800, 900-1600, 900-1400, 900-1200, 900-1000, 1000- 1900, 1000-1800, 1000-1600, 1000-1400, 1000-1200, 1200-1900, 1200-1800, 1200-1600, 1200-1400, 1400-1900, 1400-1800, 1400-1600, 1600-1900, 1600-1800 or 1800-1900.

[0076] In some respects, the glass compositions disclosed herein possess high fracture toughness. Without being bound by any particular theory, high fracture toughness can impart improved drop performance to the glass compositions. The high fracture toughness of the glass compositions described herein increases the glass's resistance to damage and allows for the application of a higher degree of stress, as characterized by central tension, to the glass through ion exchange without rendering it brittle. As used herein, unless otherwise stated, fracture toughness refers to K0 as measured by the V-notch bar method. IC Value. Used to measure K. IC The chevron notched short bar (CNSB) method is disclosed in Reddy, KPR et al., “Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens”, Journal of the American Ceramic Society (J. Am. Ceram. Soc.), 71 [6], C-310-C-313 (1988), the difference being that Y* m It was calculated using Equation 5 of Bubsey, RT et al., "Closed-Form Expressions for Crack-Mouth Displacement and Stress Intensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements," NASA Technical Memorandum 83796, pp. 1-30 (October 1992). Additionally, K was measured on unstrengthened glass samples. IC Values, such as K measured before ion exchange of a glass substrate to form a glass-based article. IC Value. Unless otherwise stated, K discussed herein is... IC Value in MPa·m 0.5 Report to the unit.

[0077] In some respects, the glass substrate possesses suitable fracture toughness (K). IC For example, in some aspects, K IC The value is at least 0.8 MPa·m0.5 In some respects, K IC Value less than 1.2 MPa·m 0.5 In some respects, K IC Value (MPa·m) 0.5 () is at least 0.8, at least 0.85, at least 0.9, at least 0.95, at least 1, at least 1.05, at least 1.1, at least 1.15, 1.2 or less, 1.15 or less, 1.1 or less, 1.05 or less, 1 or less, 0.95 or less, 0.9 or less, 0.85 or less, or any range formed therefrom. For example, in some aspects, K IC Value (MPa·m) 0.5 The values ​​are 0.8-1.2, 0.8-1.15, 0.8-1.1, 0.8-1.05, 0.8-1, 0.8-0.95, 0.8-0.9, 0.8-0.85, 0.85-1.2, 0.85-1.15, 0.85-1.1, 0.85-1.05, 0.85-1, 0.85-0.95, 0.85-0.9, 0.9-1.2, 0.9-1.15, 0.9- 1.1, 0.9-1.05, 0.9-1, 0.9-0.95, 0.95-1.2, 0.95-1.15, 0.95-1.1, 0.95-1.05, 0.95-1, 1-1.2, 1-1.15, 1-1.1, 1-1.05, 1.05-1.12, 1.05-1.15, 1.05-1.1, 1.1-1.2, 1.1-1.15 or 1.15-1.2.

[0078] The glass composition according to the embodiments has a high Young's modulus. A high Young's modulus value reduces the stored strain energy present in the glass after ion exchange. As used herein, Young's modulus (E) refers to a value measured by a general type of resonant ultrasonic spectroscopy technique as specified in ASTM E2001-13 entitled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts".

[0079] In some aspects, the glass composition has a Young's modulus of at least 84 GPa. In some aspects, the glass composition has a Young's modulus of less than 106 GPa. In some aspects, the Young's modulus value (GPa) is at least 84, at least 86, at least 88, at least 90, at least 92, at least 94, at least 96, at least 98, at least 100, at least 102, at least 104, at least 106, 106 or less, 104 or less, 102 or less, 100 or less, 98 or less, 96 or less, 94 or less, 92 or less, 90 or less, 88 or less, 86 or less, or any range thereof. For example, in some aspects, the glass composition comprises 84-106, 84-104, 84-102, 84-100, 84-98, 84-96, 84-94, 84-92, 84-90, 84-88, 84-86, 86-106, 86-104, 86-102, 86-100, 86-98, 86-96, 86-94, 86-92, 86-90, 86-88, 88-106, 88-104, 88-102, 88-100, 88-98, 88-96, 88-94, 88-92, 88-90, 90-106, 90-104, 90-102, 90-1 The Young's modulus (GPa) values ​​for 00, 90-98, 90-96, 90-94, 90-92, 92-106, 92-104, 92-102, 92-100, 92-98, 92-96, 92-94, 94-106, 94-104, 94-102, 94-100, 94-98, 94-96, 96-106, 96-104, 96-102, 96-100, 96-98, 98-106, 98-104, 98-102, 98-100, 100-106, 100-104, 100-102, 102-106, 102-104, or 104-106.

[0080] In some respects, the glass compositions described herein can form glass-based articles exhibiting an amorphous microstructure and being substantially free of crystals or microcrystals. In other words, glass-based articles formed from the glass compositions described herein can exclude glass-ceramic materials. In other respects, the glass compositions described herein can form glass-based articles containing crystals or microcrystals, such that the glass-based articles include glass-ceramic materials in some respects.

[0081] A compressive stress layer can be formed in glass by exposing it to one or more ion exchange media. In some aspects, the ion exchange media can be a molten salt bath, such as a bath containing molten nitrates. In some aspects, the ion exchange media can be a molten salt bath comprising KNO3, NaNO3, or any combination thereof. In some aspects, other sodium and potassium salts, such as sodium nitrite or potassium nitrite, sodium phosphate or potassium phosphate, or sodium sulfate or potassium sulfate, can be used in the ion exchange media. In some aspects, the ion exchange media can include lithium salts, such as LiNO3. The ion exchange media may additionally include additives typically included in ion exchange of glass, such as silicate. The ion exchange process is applied to a glass substrate to form a glass article comprising a compressive stress layer extending from the surface of the glass article to a compression depth; and a central tension region. The glass substrate used for the ion exchange process can include any of the glass compositions described herein.

[0082] In some aspects, a method for ion-exchanging a glass substrate in a first molten salt bath to form a glass article is disclosed, wherein the glass article includes a compressive stress layer extending from the surface of the glass article to a compression depth, the glass article includes a central tension region, and the glass substrate comprises any of the glass compositions disclosed elsewhere herein. In some aspects, the ion exchange is further included in a second molten salt bath following the first molten salt bath.

[0083] In some aspects, the ion exchange medium (e.g., first bath, second bath, etc.) contains at least one of NaNO3, LiNO3, and KNO3. In some aspects, the ion exchange medium contains both NaNO3 and LiNO3.

[0084] In some aspects, the ion exchange medium contains NaNO3. Typically, sodium in the ion exchange medium exchanges with lithium ions in the glass to generate compressive stress. In some aspects, the ion exchange medium (e.g., molten salt bath) contains NaNO3 in amounts (wt.%) of at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 99, 100, 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 55 or less, 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, 5 or less, or any range thereof. For example, in some aspects, the ion exchange medium content (wt.%) is 5-100, 5-95, 5-90, 5-85, 5-80, 5-75, 5-70, 5-65, 5-60, 5-55, 5-50, 5-45, 5-40, 5-35, 5-30, 5-25, 5-20, 5-15, 5-10, 10-100, 10 -95, 10-90, 10-85, 10-80, 10-75, 10-70, 10-65, 10-60, 10-55, 10-50, 10-45, 10-40, 10-35, 10-30, 10-25, 10-20, 10-15, 15-100, 15-95, 15-90, 15-80, 15-70 15-60, 15-50, 15-40, 15-30, 15-20, 20-100, 20-90, 20-80, 20-70, 20-60, 20-50, 20-40, 20-30, 30-100, 30-90, 30-80, 30-70, 30-60, 30-50, 30-40, 40-100 NaNO3 in amounts of 40-90, 40-80, 40-70, 40-60, 40-50, 50-100, 50-90, 50-80, 50-70, 50-60, 60-100, 60-90, 60-80, 60-70, 70-100, 70-90, 70-80, 80-100, 80-90, or 90-100. In some aspects, the ion exchange medium contains 100 wt.% NaNO3. Any amount of NaNO3 mentioned in this paragraph may be combined with the amounts described for KNO3 and / or LiNO3.

[0085] In some applications, the ion exchange medium contains KNO3. Typically, potassium in the ion exchange medium exchanges with sodium and / or lithium ions in the glass to generate compressive stress. In some aspects, the ion exchange medium (e.g., molten salt bath) contains (wt.%) at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 99, 100, 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 55 or less, 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, 5 or less, or any range of KNO3 formed therefrom. For example, in some aspects, the ion exchange medium content (wt.%) is 5-100, 5-95, 5-90, 5-85, 5-80, 5-75, 5-70, 5-65, 5-60, 5-55, 5-50, 5-45, 5-40, 5-35, 5-30, 5-25, 5-20, 5-15, 5-10, 10-100, 10 -95, 10-90, 10-85, 10-80, 10-75, 10-70, 10-65, 10-60, 10-55, 10-50, 10-45, 10-40, 10-35, 10-30, 10-25, 10-20, 10-15, 15-100, 15-95, 15-90, 15-80, 15-70 15-60, 15-50, 15-40, 15-30, 15-20, 20-100, 20-90, 20-80, 20-70, 20-60, 20-50, 20-40, 20-30, 30-100, 30-90, 30-80, 30-70, 30-60, 30-50, 30-40, 40-100 40-90, 40-80, 40-70, 40-60, 40-50, 50-100, 50-90, 50-80, 50-70, 50-60, 60-100, 60-90, 60-80, 60-70, 70-100, 70-90, 70-80, 80-100, 80-90, or 90-100 kJ of KNO3. In some aspects, the ion exchange medium contains 100 wt.% KNO3. Any amount of KNO3 mentioned in this paragraph may be combined with the amounts described for NaNO3 and / or LiNO3.

[0086] In some aspects, the ion exchange medium contains LiNO3. Typically, lithium ions are poisoning ions that can make the resulting glass matrix less brittle while maintaining a deeper compressibility. In some aspects, the ion exchange medium (e.g., molten salt bath) contains (wt.%) at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 99, 100, 100 or more. LiNO3 in any range of less than 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, or less, or any range thereof.For example, in some aspects, the ion exchange medium content (wt.%) is 1-10, 1-9, 1-8, 1-7, 1-6, 1-5, 1-4, 1-3, 1-2, 2-10, 2-9, 2-8, 2-7, 2-6, 2-5, 2-4, 2-3, 3-10, 3-9, 3-8, 3-7, 3-6, 3-5, 3-4, 4-10, 4-9, 4-8, 4-7, 4-6, 4-5, 5-10, 5-9, 5-8, 5-7, 5-6, 6-10, 6-9. 6-8, 6-7, 7-10, 7-9, 7-8, 8-10, 8-9, 9-10, 1-100, 5-100, 5-95, 5-90, 5-85, 5-80, 5-75, 5-70, 5-65, 5-60, 5-55, 5-50, 5-45, 5-40, 5-35, 5-30, 5-25, 5-20, 5-15, 5-10, 10-100, 10-95, 10-90, 10-85, 10-80, 10-75, 10-70 10-65, 10-60, 10-55, 10-50, 10-45, 10-40, 10-35, 10-30, 10-25, 10-20, 10-15, 15-100, 15-95, 15-90, 15-80, 15-70, 15-60, 15-50, 15-40, 15-30, 15-20, 20-100, 20-90, 20-80, 20-70, 20-60, 20-50, 20-40, 20-30, 30 LiNO3 at concentrations of -100, 30-90, 30-80, 30-70, 30-60, 30-50, 30-40, 40-100, 40-90, 40-80, 40-70, 40-60, 40-50, 50-100, 50-90, 50-80, 50-70, 50-60, 60-100, 60-90, 60-80, 60-70, 70-100, 70-90, 70-80, 80-100, 80-90, or 90-100. Any amount of LiNO3 described in this paragraph can be combined with the amounts described for NaNO3 and / or KNO3.

[0087] In some respects, as discussed elsewhere herein, the ion exchange medium (e.g., a molten salt bath) comprises a mixture of Li, Na, and K ions, which may be nitrates. For example, in some respects, the ion exchange medium comprises 1 wt.% LiNO3 and 99 wt.% NaNO3, 2 wt.% LiNO3 and 98 wt.% NaNO3, 3 wt.% LiNO3 and 97 wt.% NaNO3, 4 wt.% LiNO3 and 96 wt.% NaNO3, 5 wt.% LiNO3 and 95 wt.% NaNO3, 6 wt.% LiNO3 and 94 wt.% NaNO3, 7 wt.% LiNO3 and 93 wt.% NaNO3, or 8 wt.% LiNO3 and 92 wt.% NaNO3. Furthermore, KNO3 may be added in place of LiNO3, or additionally by replacing an equal amount of NaNO3.

[0088] In some respects, a glass substrate comprising any of the glass compositions disclosed herein can be exposed to an ion exchange medium by immersing the glass substrate in an ion exchange medium bath, spraying an ion exchange medium onto the glass substrate, or otherwise physically applying an ion exchange medium to the glass substrate, thereby forming an ion-exchanged glass article.

[0089] In some respects, the temperature of the ion exchange medium can be any suitable temperature. For example, in some respects, the temperature (°C) is at least 400, at least 410, at least 420, at least 430, at least 440, at least 450, at least 460, at least 470, at least 480, at least 490, at least 500, at least 510, at least 520, at least 530, at least 540, at least 550, 550 or lower, 540 or lower, 530 or lower, 520 or lower, 510 or lower, 500 or lower, 490 or lower, 480 or lower, 470 or lower, 460 or lower, 450 or lower, 440 or lower, 430 or lower, 420 or lower, 410 or lower, 400 or lower, or any range thereof. For example, in some aspects, the temperature (°C) is 400-550, 400-520, 400-500, 400-480, 400-460, 400-440, 400-420, 420-550, 420-540, 420-520, 420-500, 420-480, 420-450, 420-440, 420-430, 430-5 50, 430-540, 430-520, 430-500, 430-480, 430-460, 430-440, 440-550, 440-530, 440-510, 440-500, 440-490, 440-470, 440-450, 450-550, 450-530, 450-500, 450-490, 450 -480, 450-460, 460-550, 460-540, 460-520, 460-500, 460-480, 460-470, 470-550, 470-530, 470-500, 470-490, 470-480, 480-550, 480-540, 480-520, 480-500, 480-490, 4 90-550, 490-540, 490-520, 490-500, 500-550, 500-540, 500-520, 500-510, 510-550, 510-540, 510-530, 510-520, 520-550, 520-540, 520-530, 530-550, 530-540 or 540-550.

[0090] In some aspects, the ion exchange of the glass substrate in the ion exchange medium can be carried out for any suitable period of time. For example, the period of time (hours) is at least 1, at least 2, at least 4, at least 6, at least 8, at least 9, at least 10, at least 12, at least 14, at least 16, at least 18, at least 20, at least 22, at least 24, at least 25, at least 26, at least 28, at least 30, at least 32, at least 34, at least 36, at least 38, at least 40, at least 42, at least 44, at least 46, at least 48, at least 50, 50 or less, 48 ​​or more Less, 46 or less, 44 or less, 42 or less, 40 or less, 38 or less, 36 or less, 34 or less, 32 or less, 30 or less, 28 or less, 26 or less, 25 or less, 24 or less, 22 or less, 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 9 or less, 8 or less, 6 or less, 4 or less, 2 or less, or any range formed therefrom. For example, in some aspects, the time period (hours) is 1-50, 1-48, 1-40, 1-36, 1-30, 1-26, 1-18, 1-16, 1-9, 1-4, 4-48, 4-44, 4-40, 4-36, 4-30, 4-25, 4-20, 4-16, 4-12, 4-9, 4-6, 6-48, 6-42, 6-40, 6-36, 6-32, 6-30, 6-28, 6-25, 6-20, 6-16, 6-10, 8-48, 8-40, 8-36, 8-30, 8-25, 8-20, 8-14, 12-48, 12-40, 12-32, 12-24, 12-20, 12-16, 16-48, 16-40, 16- 34, 16-30, 16-25, 20-48, 20-40, 20-36, 20-25, 22-48, 22-40, 22-36, 22-32, 22-30, 22-26, 24-48, 24-46, 24-40, 24-38, 24-30, 24-26, 26-48, 26-40, 26-30, 2 6-28, 30-48, 30-40, 30-38, 30-32, 32-48, 32-46, 32-40, 32-38, 32-34, 34-48, 34-40, 34-38, 38-48, 38-46, 38-40, 40-50, 40-48, 40-46, 40-44, 40-42 or 44-48.

[0091] In some aspects, ion exchange may include a second ion exchange treatment in an ion exchange medium. In some aspects, the second ion exchange treatment may comprise any of the ion exchange media disclosed elsewhere herein (e.g., regarding composition, temperature, and time), and the conditions may be the same as or different from the first ion exchange treatment. In some aspects, the second ion exchange treatment is carried out at a lower temperature than the first ion exchange treatment; in some aspects, the second ion exchange treatment generates compressive stress spikes at the surface of the glass substrate. In some aspects, the second molten salt bath comprises NaNO3, KNO3, or a combination thereof.

[0092] In some aspects, the ion exchange process can be carried out in an ion exchange medium under processing conditions that provide the disclosed improved compressive stress distribution, for example, as disclosed in U.S. Patent Application Publication No. 2016 / 0102011, which is incorporated herein by reference in its entirety. In some aspects, the ion exchange process can be selected to form a parabolic stress distribution in glass-based articles, such as those described in U.S. Patent Application Publication No. 2016 / 0102014, which is incorporated herein by reference in its entirety.

[0093] After the ion exchange process, it should be understood that the composition of the surface of the ion-exchanged glass substrate differs from that of the formed glass substrate (i.e., the glass substrate before the ion exchange process). This is due to the presence of a certain type of alkali metal ion (e.g., Li) in the formed glass substrate. + Or Na + ) is affected by larger alkali metal ions (e.g., in Li) + In the case of Na + and / or K + And in Na + In the case of K +However, in all respects, the glass composition located at or near the deep center of the glass substrate article will generally still have the composition of the non-ion-exchanged glass substrate used to form the glass substrate article. This is because, in some respects, ion exchange typically does not occur at the center of the glass substrate article under the typical ion exchange conditions used to strengthen the glass substrate. Therefore, the composition at the center of the glass substrate article disclosed herein can be any of the glass compositions disclosed elsewhere herein (e.g., SiO2, Al2O3, MgO, CaO, Li2O, SnO2, or any combination thereof containing any amount and / or ratio of such components disclosed herein). Similarly, the properties of a glass having the same composition and microstructure as the composition at the center of the glass substrate article can be any of the properties of the glass compositions disclosed elsewhere herein (e.g., Young's modulus, fracture toughness, liquidus temperature, liquidus viscosity, etc.). As used herein, the center of the glass substrate article means any location in the glass substrate article at a distance of at least 0.5t from each of its surfaces, where t is the thickness of the glass substrate article. Typically, the center distance of a glass-based product from each of the two main surfaces is 0.5t.

[0094] As mentioned elsewhere in this document, the glass compositions described herein can be strengthened, such as through ion exchange, to produce damage-resistant glass-based articles for applications such as, but not limited to, display covers or housings (e.g., for consumer electronics devices). References Figure 1 The text describes a glass-based article having a first region under compressive stress extending from the surface of the glass-based article to a certain depth of compression (DOC). Figure 1 The first compression layer 120 and the second compression layer 122 in the DOC and the second region extending from the DOC to the center or inner region of the glass-based article under tensile stress or central tension (CT) (e.g., Figure 1 The central region 130). As used herein, DOC refers to the depth at which the stress in a glass-based article changes from compressive to tensile. At the DOC, the stress changes from positive (compressive) stress to negative (tensile) stress, and therefore the stress value is zero.

[0095] According to conventions commonly used in the art, compressive stress is expressed as a negative (< 0) stress, and tensile stress is expressed as a positive (> 0) stress. However, throughout this specification, CS is expressed as a positive or absolute value, i.e., as stated herein, CS = |CS|. The compressive stress (CS) has a maximum value at or near the surface of the glass-based article, and CS varies as a function with a distance d from the surface. (See again...) Figure 1A first segment 120 extends from a first surface 110 to a depth d1, and a second segment 122 extends from a second surface 112 to a depth d2. These segments together define the compressive stress (CS) of the glass substrate 100. Surface compressive stress (CS) can be measured using scattered light polariscope (SCALP) or refractive near-field (RNF) techniques known in the art. Unless otherwise specified, the CS values ​​provided herein are obtained using SCALP techniques. As used herein, the term "CS" refers to... k "" refers to the compressive stress at the depth of the inflection point (i.e., the transition point) as measured by RNF.

[0096] Two main surfaces ( Figure 1 The compressive stresses at 110 and 112 are balanced by the storage tension in the central region (130) of the glass substrate. The surface compressive stress (CS), maximum central tension (CT), and DOC value can be measured using the Scattered Light Polarizing Mirror (SCALP) technique or the Refractive Near Field (RNF) technique known in the art. The SCALP method or the RNF method can also be used to determine the stress distribution of the glass substrate.

[0097] In some respects, the compressive stress layer of a glass-based article contains any suitable compressive stress. For example, in some respects, the compressive stress layer contains a compressive stress of X MPa at a given compression depth or all compression depths Y, wherein X (MPa) is at least 155, at least 160, at least 165, at least 170, at least 175, at least 180, at least 185, at least 190, at least 195, at least 200, at least 205, at least 210, at least 215, at least 220, at least 225, at least 230, at least 235, at least 240, at least 245, at least 250, at least 255, at least 260, at least 265, at least 270, at least 275, at least 280, at least 285, at least 290, at least 295, at least 300, 300 or less, 295 or less, 290 or less, 285 Or less, 280 or less, 275 or less, 270 or less, 265 or less, 260 or less, 255 or less, 250 or less, 245 or less, 240 or less, 235 or less, 230 or less, 225 or less, 220 or less, 215 or less, 210 or less, 205 or less, 200 or less, 195 or less, 190 or less, 185 or less, 180 or less, 175 or less, 170 or less, 165 or less, 160 or less, 155 or less, or any range formed therefrom (e.g., 155-300, 155-290, 155-280). 155-270, 155-260, 155-250, 155-240, 155-230, 155-220, 155-210, 155-200, 155-190, 155-180, 155-170, 155-160, 160-300, 160-280, 160-260, 160-240, 160-220, 160-200, 160-180, 180-300, 180-280, 180-260, 180-240, 180-220, 180-200, 190-300, 190-290, 190-2 70, 190-250, 190-240, 190-220, 190-200, 200-300, 200-285, 200-265, 200-250, 200-230, 200-210, 210-300, 210-290, 210-280, 210-250, 210-240, 210-225, 210-220, 220-300, 220-290, 220-280, 220-260, 220-240, 240-300, 240-260, 260-300 or 280-300 compressive stress (MPa)And where Y is at least 0, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 40, at least 45, at least 50, 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, 5 or less, or any range of compression depth (micrometers) formed therefrom (e.g., 0-50, 0-45, 0-40, 0-35, 0-30, 0-25, 0-20, 0-15, 0-10, 0-5, 5-50, 5-45, 5-40, 5-35, 5-30, 5-25, 5-20, 5-15, 5-10). Compression depth (micrometers) of 10-50, 10-45, 10-40, 10-35, 10-30, 10-25, 10-20, 10-15, 15-50, 15-45, 15-40, 15-35, 15-30, 15-25, 15-20, 20-50, 20-45, 20-40, 20-35, 20-30, 20-25, 25-50, 25-45, 25-40, 25-35, 25-30, 30-50, 30-45, 30-40, 30-35, 35-50, 35-45, 35-40, 40-50, 40-50, 40-45 or 45-50. For example, in some aspects, the compressive stress layer may contain at least 155 MPa of compressive stress across all compressive depths from 0 to 45 micrometers. In some aspects, the compressive stress layer contains at least 10 micrometers of compressive depth, and in some aspects, it contains at least 155 MPa of compressive stress across all compressive depths between 10 and 50 micrometers.

[0098] In some aspects, the compressive stress layer of the glass-based article contains any suitable maximum surface compressive stress (i.e., at the main surface of the glass-based article). For example, in some aspects, the compressive stress layer contains a maximum surface compressive stress (MPa) of at least 800, at least 850, at least 900, at least 950, at least 1000, at least 1050, at least 1100, at least 1150, at least 1200, at least 1250, at least 1300, 1300 or less, 1250 or less, 1200 or less, 1150 or less, 1100 or less, 1050 or less, 1000 or less, 950 or less, 900 or less, 850 or less, 800 or less, or any range thereof. For example, in some aspects, the maximum surface compressive stress (MPa) is 800-1300, 800-1250, 800-1200, 800-1150, 800-1100, 800-1050, 800-1000, 800-950, 800-900, 800-850, 850-1300, 850-1250, 850-1 200, 850-1150, 850-1100, 850-1050, 850-1000, 850-950, 850-900, 900-1300, 900-1250, 900-1200, 900-1150, 900-1100, 900-1050, 900-1000, 900-950, 950-13 00, 950-1250, 950-1200, 950-1150, 950-1100, 950-1050, 950-1000, 1000-1300, 1000-1250, 1000-1200, 1000-1150, 1000-1100, 1000-1050, 1050-1300, 1050-1 250, 1050-1200, 1050-1150, 1050-1100, 1100-1300, 1100-1250, 1100-1200, 1100-1150, 1150-1300, 1150-1250, 1150-1200, 1200-1300, 1200-1250 or 1250-1300.

[0099] In some aspects, the compressive stress layer of a glass-based article contains compressive stress spikes that extend from the surface of the glass-based article to a certain depth, and the depth of the compressive stress spike is any suitable depth. The compressive stress at which the spike transitions from a high slope to a low slope is called the inflection point compressive stress (CS). k ), and it was precisely in this CS kDepth is measured from the surface. For example, in some aspects, the depth (micrometers) is at least 1, at least 1.5, at least 2, at least 2.5, at least 3, at least 3.5, at least 4, at least 4.5, at least 5, at least 5.5, at least 6, at least 6.5, at least 7, at least 7.5, at least 8, at least 8.5, at least 9, at least 9.5, at least 10, 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, or any range formed therefrom. For example, in some aspects, the depth is 1-10, 1-9, 1-8, 1-7, 1-6, 1-5, 1-4, 1-3, 1-2, 2-10, 2-9, 2-8, 2-7, 2-6, 2-5, 2-4, 2-3, 3-10, 3-9, 3-8, 3-7, 3-6, 3-5, 3-4, 4-10, 4-9, 4-8, 4-7, 4-6, 4-5, 5-10, 5-9, 5-8, 5-7, 5-6, 6-10, 6-9, 6-8, 6-7, 7-10, 7-9, 7-8, 8-10, 8-9, or 9-10.

[0100] In some aspects, the tensile stress region of the glass-based articles disclosed herein can have any suitable maximum central tension. For example, in some aspects, the tensile stress region of the glass-based articles comprises at least 50, at least 555, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 100, at least 105, at least 110, at least 115, at least 120, at least 125, at least 130, at least 135, at least 140, at least 145, at least 150, at least 155, at least 160, at least 165, at least 170, at least 175, at least 180, at least 185, at least 190, at least 195, 200 or less, 195 or less. 190 or less, 185 or less, 180 or less, 175 or less, 170 or less, 165 or less, 160 or less, 155 or less, 150 or less, 145 or less, 140 or less, 135 or less, 130 or less, 125 or less, 120 or less, 115 or less, 110 or less, 105 or less, 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 55 or less, or any range of maximum center tension (MPa). For example, the maximum center tension (MPa) can be 50-200, 50-190, 50-180, 50-170, 50-160, 50-150, 50-140, 50-130, 50-120, 50-110, 50-100, 50-90, 50-80, 50-70, 50-60, 60-200, 60-180, 60-160, 60-140, 60-120, 60-100, 60-8 0, 80-200, 80-180, 80-160, 80-140, 80-120, 80-100, 100-200, 100-180, 100-160, 100-140, 100-120, 120-200, 120-180, 120-160, 120-140, 140-200, 140-180, 140-160, 160-200, 160-180 or 180-200.

[0101] In some respects, the compressive stress layer of the glass-based article comprises a compression depth (DOC) (micrometers) of at least 50, at least 55, at least 60, at least 65, at least 70, at least 75, at least 80, at least 85, at least 90, at least 95, at least 100, at least 105, at least 110, at least 115, at least 120, at least 125, 130 or less, 125 or less, 120 or less, 115 or less, 110 or less, 105 or less, 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 55 or less, or any range thereof. For example, in some aspects, the compressive stress layer (DOC) (micrometers) is 50-130, 50-120, 50-110, 50-105, 50-95, 50-80, 50-65, 50-55, 55-130, 55-125, 55-115, 55-110, 55-100, 55-95, 55-85, 55-808, 55-75, 55-65, 55-60, 60-130, 60-120, 60-95, 60-85, 60-70, 60-65, 65-130, 65-120, 65-11 0, 65-100, 65-95, 65-85, 65-70, 70-130, 70-120, 70-100, 70-90, 70-85, 70-75, 75-130, 75-120, 75-100, 75-95, 75-90, 75-80, 90-130, 90-120, 90-100, 100-130, 100-120, 100-110, 110-130, 110-125, 110-115, 115-130, 115-125, 115-120 or 120-130.

[0102] In some aspects, the depth of compression (DOC) is provided as a part of the thickness (t) of the glass-based article. In some aspects, the DOC of the glass-based article can be at least 0.05t, at least 0.06t, at least 0.08t, at least 0.1t, at least 0.12t, at least 0.14t, at least 0.16t, at least 0.18t, at least 0.2t, at least 0.22t, at least 0.24t, at least 0.25t, 0.25t or less, 0.24t or less, 0.22t or less, 0.2t or less, 0.18t or less, 0.16t or less, 0.14t or less, 0.12t or less, 0.1t or less, 0.08t or less, 0.06t or less, or any range thereof. For example, in some aspects, the proportion of DOC to t is 0.05-0.25, 0.05-0.24, 0.05-0.22, 0.05-0.2, 0.05-0.18, 0.05-0.16, 0.05-0.14, 0.05-0.12, 0.05-0.1, 0.05-0.08, 0.05-0.06, 0.06-0.25, 0.06-0.24, 0.06-0.22, and 0.06-0.2. 0.06-0.18, 0.06-0.16, 0.06-0.14, 0.06-0.12, 0.06-0.1, 0.06-0.08, 0.08-0.25, 0.08-0.24, 0.08-0.22, 0.08-0.2, 0.08-0.18, 0.08-0.16, 0.08-0.14, 0.08-0.12, 0.08-0.1, 0.1-0.25, 0.1-0.2 4, 0.1-0.22, 0.1-0.2, 0.1-0.18, 0.1-0.16, 0.1-0.14, 0.1-0.12, 0.12-0.25, 0.12-0.24, 0.12-0.22, 0.12-0.2, 0.12-0.18, 0.12-0.16, 0.12-0.14, 0.14-0.25, 0.14-0.24, 0.14-0.22, 0.14-0.2, 0 0.14-0.18, 0.14-0.16, 0.16-0.25, 0.16-0.24, 0.16-0.22, 0.16-0.2, 0.16-0.18, 0.18-0.25, 0.18-0.24, 0.18-0.22, 0.18-0.2, 0.2-0.25, 0.2-0.24, 0.2-0.22, 0.22-0.25, 0.22-0.24, or 0.24-0.25. As used herein, DOC can also be expressed as DOC / t (where DOC and t have the same unit, such as micrometers or millimeters), where any of the values ​​preceding t in this paragraph is equal to DOC / t by simple algebra.

[0103] In some respects, glass-based articles can have any suitable thickness (t). For example, in some respects, the thickness t (mm) of glass-based articles is at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1, at least 1.2, at least 1.4, at least 1.6, at least 1.8, at least 2, 2 or less, 1.8 or less, 1.6 or less, 1.4 or less, 1.2 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or any range formed therefrom. For example, in some aspects, the thickness t (mm) of glass-based products is 0.2-2, 0.2-1.8, 0.2-1.6, 0.2-1.4, 0.2-1.2, 0.2-1, 0.2-0.8, 0.2-0.6, 0.2-0.5, 0.2-0.3, 0.3-2, 0.3-1.8, 0.3-1.6, 0.3-1.4, 0.3-1, 0.3-0.9, 0.3-0.7, 0.3-0.5, 0.3-0.4, 0.4-2, 0.4-1.8, 0.4-1.6, 0.4-1.4, 0.4-1.2, 0.4-1, 0.4-0.9, 0.4-0.7, 0.4-0.5, 0.5-2, 0.5-1.8, 0.5-1.2, 0.5-1, 0.5-1.9 0.5-1.7, 0.5-1.6, 0.6-2, 0.6-1.8, 0.6-1.6, 0.6-1.2, 0.6-1, 0.6-0.9, 0.6-0.7, 0.7-2, 0.7-1.8, 0.7-1.4, 0.7-1.2, 0.7-0.9, 0.7-0.8, 0.8-2, 0.8-1.6, 0.8-1.2 0.8-0.9, 0.9-2, 0.9-1.6, 0.9-1.2, 0.9-1, 1-2, 1-1.8, 1-1.6, 1-1.4, 1-1.2, 1.2-2, 1.2-1.8, 1.2-1.6, 1.2-1.4, 1.4-2, 1.4-1.8, 1.4-1.6, 1.6-2, 1.6-1.8 or 1.8-2.

[0104] In some aspects, the glass-based article has a compressive stress layer containing compressive stress, and the integral of the compressive stress is any suitable number. For example, in some aspects, the integral of the compressive stress from 6 micrometers (or from 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 micrometers) to the compressive depth is at least 10, at least 10.3, at least 10.5, at least 11, at least 11.5, at least 12, at least 12.5, at least 13, at least 13.5, at least 14, at least 14.5, at least 15, at least 16, at least 18, at least 20, 20 or less, 18 or less, 16 or less, 15 or less, 14.5 or less, 14 or less, 13.5 or less, 13 or less, 12.5 or less, 12 or less, 11.5 or less, 11 or less, 10.5 or less, 10.3 or less, 10 or less, or any range formed therefrom.For example, the integral of compressive stress from 6 micrometers (or from 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 micrometers) to the compression depth is 10⁻²⁰, 10⁻¹⁸, 10⁻¹⁶, 10⁻¹⁵, 10⁻¹⁴.5, 10⁻¹⁴, 10⁻¹³.5, 10⁻¹³, ​​10⁻¹².5, 10⁻¹², 10⁻¹¹.5, 10⁻¹¹, 10⁻¹⁰.5, 10⁻¹⁰.3, 10.3⁻²⁰, 10.3⁻¹⁸, 10.3⁻¹⁶, 10.3⁻¹⁵, 10.3⁻¹⁴.5, 10.3⁻¹⁴, 10.3⁻¹³.5, 1 0.3-13, 10.3-12.5, 10.3-12, 10.3-11.5, 10.3-11, 10.3-10.5, 10.5-20, 10.5-18, 10.5-16, 10.5-15, 10.5-14.5, 10.5-14, 10.5-13.5, 10.5-13, 10.5-12.5, 10.5-12, 10.5-11.5, 10.5-11, 11-20, 11-18, 11-16, 11-15, 11-14.5, 11-14, 11-13.5, 11-13, 11-12 0.5, 11-12, 11-11.5, 11.5-20, 11.5-18, 11.5-16, 11.5-15, 11.5-14.5, 11.5-14, 11.5-13.5, 11.5-13, 11.5-12.5, 11.5-12, 12-20, 12-18, 12-16, 12-15, 12-14.5, 12-14, 12-13.5, 12-13, 12-12.5, 12.5-20, 12.5-18, 12.5-16, 12.5-15, 12.5-14.5, 12.5-14 12.5-13.5, 12.5-13, 13-20, 13-18, 13-16, 13-15, 13-14.5, 13-14, 13-13.5, 13.5-20, 13.5-18, 13.5-16, 13.5-15, 13.5-14.5, 13.5-14, 14-20, 14-18, 14-16, 14-15, 14-14.5, 14.5-20, 14.5-18, 14.5-16, 14.5-15, 15-20, 15-18, 15-16, 16-20, 16-18 or 18-20. For clarity, integration is performed using computer software to integrate the area under the curve of the resulting compressive stress versus the compression depth distribution, for example using RNF, where the stress is in MPa and the depth is in micrometers.

[0105] In some respects, Na + and K +Ions are exchanged into the glass-based product, and Na... + Ion ratio K + Ions diffuse deeper into glass-based products. K + The depth of ion penetration (“potassium DOL”) differs from DOC because it represents the depth of potassium penetration resulting from the ion exchange process. For the articles described herein, potassium DOL is typically less than DOC. Potassium DOL can be measured using a surface stress meter, such as the commercially available FSM-6000 surface stress meter manufactured by Orihara Industrial Co., Ltd. (Japan), which relies on accurate measurement of the stress optical coefficient (SOC). Potassium DOL can be defined as the depth of compressive stress peak (DOL). SP The stress distribution transitions from a steep, peaked region to a less steep, deeper region. This deeper region extends from the base of the peak to the compression depth. (DOL of glass-based articles) SP It can be greater than or equal to 3 µm to less than or equal to 10 µm, such as greater than or equal to 4 µm to less than or equal to 9 µm, greater than or equal to 5 µm to less than or equal to 8 µm, greater than or equal to 6 µm to less than or equal to 7 µm, and all ranges and subranges between the aforementioned values.

[0106] In some respects, the glass-based articles disclosed herein can be incorporated into another type of article, such as articles having a display (or display articles) (e.g., consumer electronic devices, including mobile phones, tablets, computers, navigation systems, etc.), building articles, transport articles (e.g., automobiles, trains, airplanes, ships, etc.), appliance articles, or any article requiring a certain degree of transparency, scratch resistance, abrasion resistance, or a combination thereof. Exemplary articles incorporated into any of the glass-based articles disclosed herein are shown in [illustration / example]. Figure 2A and 2B . Specifically, Figure 2A and 2B A consumer electronic device 200 is shown, comprising a housing 202 having a front surface 204, a rear surface 206, and a side surface 208; electrical components (not shown) at least partially or entirely within the housing, including at least a controller, memory, and a display 210 located at or near the front surface of the housing; and a cover 212 at or above the front surface of the housing, such that it is positioned above the display. In some aspects, at least a portion of at least one of the cover 212 and the housing 202 may comprise any of the glass-based articles described herein.

[0107] This article considers various aspects, some of which are elaborated in the following paragraphs. With explicit consideration, any aspect or part thereof can be combined to form a combination.

[0108] Aspect 1: A type of glass comprising:

[0109] 57-68 mol.% SiO2;

[0110] 9.5-16 mol.% Al2O3;

[0111] At least 8 mol.% MgO;

[0112] At least 7 mol.% CaO;

[0113] At least 7 mol.% Li₂O; and

[0114] Less than 4 mol.% Na2O.

[0115] Aspect 2: Glass according to aspect 1 or any of the foregoing aspects, comprising 58-63 mol.% Si2O.

[0116] Aspect 3: Glass according to aspect 1 or 2 or any of the foregoing aspects, comprising 9.5-13 mol.% Al2O3.

[0117] Aspect 4: Glass according to any one of Aspects 1 to 3 or any of the foregoing aspects, comprising 8-30 mol.% MgO.

[0118] Aspect 5: Glass according to any one of Aspects 1 to 4 or any of the foregoing aspects, comprising 7-20 mol.% CaO.

[0119] Aspect 6: Glass according to any one of aspects 1 to 5 or any of the preceding aspects, comprising 6-20 mol.% Li2O.

[0120] Aspect 7: Glass according to any one of Aspects 1 to 6 or any of the foregoing aspects, comprising >0-1 mol.%SnO2.

[0121] Aspect 8: Glass according to any one of Aspects 1 to 7 or any of the foregoing aspects, containing less than 2 mol.% Na2O.

[0122] Aspect 9: The glass according to any one of aspects 1 to 8 or any of the foregoing aspects, comprising:

[0123] 58-63 mol.% SiO2;

[0124] 9.5-13 mol.% Al2O3;

[0125] 8-15 mol.% MgO;

[0126] 7-15 mol.% CaO;

[0127] 7-15 mol.% Li₂O; and

[0128] Less than 1 mol.% Li2O.

[0129] Aspect 10: The glass according to any one of Aspects 1 to 9 or any of the foregoing aspects comprises at least one of the following:

[0130] 0.5-1.5 R2O / Al2O3;

[0131] The RO / Al2O3 ratio must be at least 1.4.

[0132] The ratio of (RO + R2O) / Al2O3 is at least 2;

[0133] The amounts are expressed in mol.%; R2O is the total amount of Li2O, Na2O, K2O, Rb2O and Cs2O in the glass, and RO is the total amount of MgO, CaO, SrO and BaO in the glass.

[0134] Aspect 11: Glass according to any one of Aspects 1 to 10 or any of the foregoing aspects, wherein the glass is substantially free of at least one of ZrO2, Y2O3, La2O3, Na2O, K2O, P2O5, SrO and B2O3.

[0135] Aspect 12: Glass according to any one of Aspects 1 to 11 or any of the foregoing aspects, having a Young's modulus of 84-106 GPa.

[0136] Aspect 13: Glass according to any one of Aspects 1 to 12 or any of the foregoing aspects, having a liquidus temperature of 1000-1300°C.

[0137] Aspect 14: Glass according to any one of Aspects 1 to 13 or any of the foregoing aspects, having a liquidus viscosity of 800-1900 poise.

[0138] Aspect 15: A method for ion exchange of a glass substrate, the method comprising:

[0139] The glass substrate is subjected to ion exchange in a first molten salt bath to form a glass-based article.

[0140] The glass substrate includes a compressive stress layer extending from the surface of the glass substrate to a certain compression depth, the glass substrate includes a central tension region, and the glass substrate comprises glass according to any one of aspects 1 to 14 or any of the foregoing aspects.

[0141] Aspect 16: The method according to aspect 15 or any of the preceding aspects, wherein the first molten salt bath comprises NaNO3.

[0142] Aspect 17: The method according to aspect 15 or 16 or any of the preceding aspects, wherein the first molten salt bath comprises NaNO3 and LiNO3.

[0143] Aspect 18: The method according to aspect 15 or 16 or any of the preceding aspects, wherein the first molten salt bath contains 100 wt.% NaNO3.

[0144] Aspect 19: The method according to any one of Aspects 15 to 17 or any of the preceding aspects, wherein the first molten salt bath comprises KNO3.

[0145] Aspect 20: The method according to any one of aspects 15 to 19 or any of the preceding aspects, wherein the first molten salt bath is at a temperature of 400-550°C.

[0146] Aspect 21: The method according to any one of aspects 15 to 20 or any of the preceding aspects, wherein the ion exchange lasts for a period of 1 to 48 hours.

[0147] Aspect 22: The method according to any one of aspects 15 to 21 or any of the preceding aspects, wherein the ion exchange further comprises a second molten salt bath following the first molten salt bath.

[0148] Aspect 23: The method according to aspect 22 or any of the preceding aspects, wherein the temperature of the second molten salt bath is lower than the temperature of the first molten salt bath.

[0149] Aspect 24: The method according to aspect 22 or 23 or any of the preceding aspects, wherein the second molten salt bath comprises NaNO3, KNO3 or a combination thereof.

[0150] Aspect 25: A glass-based article comprising:

[0151] A compressive stress layer, the compressive stress layer extending from the surface of the glass substrate to a certain compression depth;

[0152] Central tension region; and

[0153] The composition located at the center of the glass-based article, the composition comprising:

[0154] 57-68 mol.% SiO2;

[0155] 9.5-16 mol.% Al2O3;

[0156] At least 8 mol.% MgO;

[0157] At least 7 mol.% CaO;

[0158] At least 7 mol.% Li₂O; and

[0159] Less than 4 mol.% Na2O.

[0160] Aspect 26: A glass-based article according to aspect 25 or any of the preceding aspects, wherein the compressive stress layer contains a compressive stress of at least 155 MPa at a compression depth of at least 10 micrometers.

[0161] Aspect 27: A glass-based article according to aspect 25 or 26 or any of the preceding aspects, wherein the compressive stress layer contains a compressive stress of at least 155 MPa at all compression depths from 0 to 45 micrometers.

[0162] Aspect 28: A glass-based article according to any one of Aspects 25 to 27 or any of the preceding aspects, wherein the compressive stress layer contains a maximum surface compressive stress of at least 800 MPa.

[0163] Aspect 29: A glass-based article according to any one of Aspects 25 to 28 or any of the preceding aspects, wherein the compressive stress layer comprises compressive stress peaks extending from the surface of the glass-based article to a certain compressive stress peak depth, and the compressive stress peak depth is 2-10 micrometers.

[0164] Aspect 30: A glass-based article according to any one of Aspects 25 to 29 or any of the foregoing aspects, wherein the central tension region contains a maximum central tension of 50-200 MPa.

[0165] Aspect 31: A glass-based article according to any one of Aspects 25 to 30 or any of the foregoing aspects, wherein the compression depth is 50-130 micrometers.

[0166] Aspect 32: A glass-based article according to any one of Aspects 25 to 31 or any of the preceding aspects, wherein the compression depth is 0.05t-0.25t, where t is the thickness of the glass-based article.

[0167] Aspect 33: A glass-based article according to any one of aspects 25 to 32 or any of the preceding aspects, wherein the thickness t of the glass-based article is 0.2-2 mm.

[0168] Aspect 34: A glass-based article according to any one of Aspects 25 to 33 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises 58-64 mol.% Si2O.

[0169] Aspect 35: A glass-based article according to any one of Aspects 25 to 34 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises 9.5-14 mol.% Al2O3.

[0170] Aspect 36: A glass-based article according to any one of Aspects 25 to 35 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises 8-30 mol.% MgO.

[0171] Aspect 37: A glass-based article according to any one of Aspects 25 to 36 or any of the preceding aspects, wherein the composition at the center of the glass-based article comprises 7-20 mol.% CaO.

[0172] Aspect 38: A glass-based article according to any one of Aspects 25 to 37 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises 7-20 mol.% Li2O.

[0173] Aspect 39: A glass-based article according to any one of Aspects 25 to 38 or any of the preceding aspects, wherein the composition at the center of the glass-based article contains >0-1 mol.% SnO2.

[0174] Aspect 40: A glass-based article according to any one of Aspects 25 to 39, wherein the composition at the center of the glass-based article contains less than 2 mol.% Na2O.

[0175] Aspect 41: A glass-based article according to any one of aspects 25 to 40 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises:

[0176] 58-63 mol.% SiO2;

[0177] 9.5-13 mol.% Al2O3;

[0178] 8-15 mol.% MgO;

[0179] 7-15 mol.% CaO;

[0180] 7-15 mol.% Li₂O; and

[0181] Less than 1 mol.% Na2O.

[0182] Aspect 42: A glass-based article according to any one of aspects 25 to 41 or any of the foregoing aspects, wherein the composition at the center of the glass-based article comprises at least one of the following:

[0183] 0.5-1.5 R2O / Al2O3;

[0184] The RO / Al2O3 ratio must be at least 1.4.

[0185] The ratio of (RO + R2O) / Al2O3 is at least 2;

[0186] The amounts are expressed in mol.%; R2O is the total amount of Li2O, Na2O, K2O, Rb2O and Cs2O in the glass, and RO is the total amount of MgO, CaO, SrO and BaO in the glass.

[0187] Aspect 43: A glass-based article according to any one of aspects 25 to 42 or any of the preceding aspects, wherein the composition at the center of the glass-based article comprises substantially free of at least one of ZrO2, Y2O3, La2O3, Na2O, K2O, P2O5, SrO and B2O3.

[0188] Aspect 44: A glass-based article according to any one of Aspects 25 to 43 or any of the foregoing aspects, wherein the glass having the same composition and microstructure as the composition at the center of the glass-based article has a Young's modulus of 84-106 GPa.

[0189] Aspect 45: A glass-based article according to any one of aspects 25 to 44 or any of the preceding aspects, wherein the liquidus temperature of the glass having the same composition and microstructure as the composition at the center of the glass-based article is 1000-1300°C.

[0190] Aspect 46: A glass-based article according to any one of Aspects 25 to 45 or any of the foregoing aspects, wherein the liquidus viscosity of the glass having the same composition and microstructure as the composition at the center of the glass-based article is 800-1900 poise.

[0191] Aspect 47: A glass-based article according to any one of Aspects 25 to 46 or any of the preceding aspects, wherein the compressive stress layer comprises compressive stress, and the integral of the compressive stress, in MPa, from 6 micrometers (or from 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 micrometers) to the compression depth is at least 10.5.

[0192] Aspect 48: A consumer electronics product comprising:

[0193] The housing has a front surface, a rear surface, and side surfaces;

[0194] Electrical components, at least partially disposed within the housing, the electrical components including at least a controller, a memory, and a display, the display being disposed on or adjacent to the front surface of the housing; and

[0195] A cover plate, which is disposed above the display;

[0196] At least a portion of the housing and the cover substrate comprises a glass-based article according to any one of aspects 25 to 47 or any of the foregoing aspects.

[0197] Aspect 49: A combination of any two or more of the foregoing aspects or any part thereof.

[0198] Example

[0199] The following examples illustrate non-limiting aspects of this disclosure and are not intended to limit the scope of this disclosure or the claims.

[0200] Example 1 This example illustrates the preparation and analysis of a glass composition.

[0201] The glass composition comprises the components listed in Table 1 below and is prepared by conventional glass forming methods. In Table 1, all components are expressed in mol%. The liquidus temperature and liquidus viscosity were measured according to the methods described herein. The Poisson's ratio (ν), Young's modulus (E), and shear modulus (G) of the glass composition were measured using a general type of resonant ultrasonic spectroscopy technique as specified in ASTM E2001-13, entitled "Standard Guide for the Detection of Defects in Both Metallic and Nonmetallic Parts." Table 1 also reports the refractive index and stress optical coefficient (SOC) of the substrate at 589.3 nm. The refractive index was measured using a PerkinElmer 950 spectrometer. The SOC was measured according to Procedure C (Glass Disk Method) as described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient." The density of the glass composition was determined using the buoyancy method of ASTM C693-93 (2013).

[0202] Table 1

[0203]

[0204]

[0205] Example 2This example demonstrates the properties of ion-exchange glass compositions A and B of Example 1 at different temperatures and times.

[0206] A substrate with a thickness of 1.0 mm was formed from the compositions in Table 1, and then ion exchange was performed to form an example article. The ion exchange involved immersing the substrate in a molten salt bath.

[0207] Specifically, in one example, a 1.0 mm thick substrate having compositions A and B was immersed in a molten salt bath containing 100 wt.% NaNO3, and the time and temperature are shown in Table 2. Table 2 also shows the weight gain caused by the ion exchange treatment, as well as the maximum central tension (CT) measured using a Scattered Light Polarizing Microscope (SCALP).

[0208] Table 2

[0209]

[0210] Example 3 This example further illustrates the ion-exchange glass compositions A and B of Example 1, sustained at a temperature for different times, and the resulting properties.

[0211] A 1.0 mm thick substrate having compositions A and B was immersed in a molten salt bath containing 100 wt.% NaNO3 at 470°C for the durations shown in Table 3. For ion-exchanged articles, Table 3 also shows the weight gain due to ion-exchange treatment, the maximum center tension (CT) measured by SCALP, and the depth of compression (DOC) measured by refractive near-field (RNF) techniques known in the art. Figure 3 and Figure 4 The RNF distributions of ion-exchanged samples A and B are shown, respectively, which show the compressive stress (CS) as a function of depth.

[0212] Table 3

[0213]

[0214] Example 4 This example illustrates the ion-exchange glass compositions A, B, C, D, and F of Example 1 and the resulting properties.

[0215] 0.5 mm thick substrates containing compositions A and B were immersed in a molten salt bath containing 100 wt.% NaNO3 at 470 °C for 9, 16, and 25 hours. Although the 9-hour sample was critically brittle, and the 9-hour and 25-hour samples were brittle, all samples at all three time periods exhibited significantly higher compressive stress than the comparative glass compositions C, D, and F discussed below.

[0216] Three comparative 0.5 mm thick substrates containing compositions C, D, and F were also subjected to ion exchange as follows. Composition C substrate underwent a two-step ion exchange (DIOX), wherein the first step was carried out for 16 hours at 600°C in a mixed nitrate-sulfate molten salt bath with a sodium:potassium ion molar ratio of 35:65. The second step was carried out for 10 minutes at 370°C in a molten salt bath containing 100 wt.% KNO3. In the first step, a mixed nitrate-sulfate bath was used to prevent significant degradation or decomposition of the salt at 600°C. The composition in the mixed nitrate-sulfate bath in the first step contained 25.6 wt.% NaNO3, 47.6 wt.% KNO3, 9.2 wt.% Na2SO4, and 17.6 wt.% K2SO4. The D substrate of composition was subjected to single-step ion exchange (SIOX) at 450°C for 4-5 hours in a molten salt bath containing 9 wt.% NaNO3, 90.5 wt.% KNO3, and 0.5 wt.% LiNO3. The F substrate of composition was subjected to DIOX, wherein the first step was carried out at 440°C for 75 minutes in a molten salt bath containing 50 wt.% NaNO3 and 50 wt.% KNO3, followed by a second step at 390°C for 10-15 minutes in a molten salt bath containing 2 wt.% NaNO3 and 98 wt.% KNO3.

[0217] The RNF compressive stress distribution of the ion-exchanged articles was measured, and the stress distribution of articles made from composition A was plotted. Figure 5 In, and for articles made of composition B, it is depicted in Figure 6 As can be seen from these figures, the CS of articles made from compositions A and B is much higher than that of articles made from compositions C, D, and F, especially for ion exchange times of 16 hours and 25 hours, at most depths below approximately 90 micrometers.

[0218] The results are also listed in Table 4 below.

[0219] Table 4.

[0220]

[0221] Example 5 This example demonstrates an ion-exchange 0.5 mm glass substrate made from glass compositions D, E, and F of Example 1 and compositions G and H listed in Table 5 below. The resulting properties are also reported.

[0222] Table 5

[0223]

[0224] 0.5 mm thick glass substrates with compositions D, E, F, G, and H were prepared using the procedure described in Example 1. Note that compositions G and H are similar to compositions A and B, respectively. The substrates with compositions G and H were immersed in a molten salt bath according to the ion exchange (IOX) conditions shown in Table 6. Some measurements were performed in duplicate, resulting in Samples 1 and 2. The maximum center tension (CT) of these ion-exchanged articles was then analyzed, as measured by SCALP, the depth of compression (DOC) as measured by RNF, and the percentage increase in weight. DOC / t is the ratio of depth of compression to thickness (t), where both DOC and t are in micrometers. The results are reported in Table 6.

[0225] Table 6

[0226]

[0227] Three comparative 0.5 mm thick substrates with compositions D, E, and F were also subjected to ion exchange. Ion exchange was performed on substrates of compositions D and F as described in Example 4. Substrate of composition E was subjected to DIOX, wherein the first step was carried out for 8 hours at 480°C in a molten salt bath containing 20 wt.% NaNO3, 79.9 wt.% KNO3, and 0.1 wt.% LiNO3, followed by a second step carried out for 2 hours at 490°C in a molten salt bath containing 5 wt.% NaNO3 and 95 wt.% KNO3.

[0228] The RNF compressive stress distribution of ion-exchanged articles containing compositions D, E, F, and H was measured, and these results were depicted in... Figure 7 Various comparisons between 0.5 mm thick glass-based articles made of composition H and comparative articles are listed in Tables 7 and 8.

[0229] Table 7

[0230]

[0231] from Figure 7 As can be seen from Table 7, the CS of articles made from composition H is much higher than that of articles made from compositions D, E and F, especially at most depths below about 80 micrometers.

[0232] Table 8

[0233]

[0234] As can be seen from Table 8, compared with comparative products D, E, and F, the glass-based product prepared from composition H has a significantly higher area under the stress curve, indicating that the composition of the present invention has significantly greater compressive stress. The higher amount of compressive stress expressed by this integral indicates that the glass-based product of the present invention is more resistant to bending and sharp impact failure.

[0235] It should be understood that the disclosed aspects or embodiments may relate to specific features, elements, or steps described in connection with a particular aspect or embodiment. It should also be understood that although a particular aspect or embodiment has been described, specific features, elements, or steps may be interchanged or combined with alternative aspects or embodiments in various combinations or arrangements not shown.

[0236] As used herein, when the term “and / or” is used in a list of two or more items, it means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B and / or C, the composition may contain only A; only B; only C; a combination of A and B; a combination of A and C; a combination of B and C; or a combination of A, B and C.

[0237] While the transitional phrase "comprising" may be used to disclose various features, elements, or steps of a particular aspect or embodiment, it should be understood that implicit alternative aspects or embodiments include those described using the transitional phrases "comprising" or "substantially comprising." Thus, for example, implicit alternative aspects or embodiments of a device comprising A+B+C include aspects or embodiments of the device comprising A+B+C and aspects or embodiments of the device substantially comprising A+B+C.

[0238] References to the position of elements herein (e.g., “top,” “bottom,” “above,” “below,” “first,” “second,” etc.) are used only to describe the orientation of the various elements in the accompanying drawings. It should be noted that the orientation of the various elements may differ according to other exemplary embodiments, and such variations are intended to be covered by this disclosure. Furthermore, these relational terms are used only to distinguish one entity or action from another, and do not necessarily require or imply any actual such relationship or order between such entities or actions.

[0239] As used herein, the terms “about,” “approximately,” “substantially,” and similar terms are intended to have a broad meaning consistent with common and accepted usage by one of ordinary skill in the art to which the subject matter of this disclosure pertains. Those skilled in the art who have examined this disclosure will understand that these terms are intended to allow for description of certain features described and claimed, without limiting the scope of those features to the precise numerical ranges provided. Therefore, these terms should be interpreted as indicating that non-substantial or insignificant modifications or alterations to the described and claimed subject matter are considered to fall within the scope of the invention as set forth in the appended claims.

[0240] As used herein, terms such as “optional,” “optionally,” etc., are intended to mean that the event or condition subsequently described may or may not occur, and the description includes examples of the event or condition occurring as well as examples of the event or condition not occurring. As used herein, unless otherwise specified, the indefinite articles “a,” “an,” and the corresponding definite article “described” mean “at least one / a” or “one or more / a.” It should also be understood that the various features disclosed in the specification and figures can be used in any and all combinations.

[0241] Regarding the use of any plural and / or singular terms in this document, those skilled in the art can convert from plural to singular and / or from singular to plural as appropriate to the context and / or application. For clarity, different single / multiple substitutions may be explicitly described herein.

[0242] Unless otherwise specified, all compositions are expressed as a batch weight percentage (wt.%). As will be understood by those skilled in the art, various melt components (e.g., silicon, alkali or alkaline earth metal-based, boron, etc.) can undergo varying levels of volatilization during melting (e.g., varying with vapor pressure, melting time, and / or melting temperature). Therefore, the batch weight percentage values ​​used in relation to such components are intended to cover values ​​of these components within ±0.5 wt.% of the final melted article of production. In light of the foregoing, substantial compositional equivalence is expected between the final article of production and the batch composition.

[0243] It will be apparent to those skilled in the art that various modifications and variations can be made to this disclosure without departing from its spirit and scope. Since modifications, combinations, sub-combinations, and variations of the disclosed embodiments incorporating the spirit and intent of this disclosure will be readily apparent to those skilled in the art, this disclosure should be construed as including all contents within the scope of the appended claims and their equivalents.

Claims

1. A type of glass comprising: 57-68 mol.% SiO2; mol.% Al2O3; At least 8 mol.% MgO; At least 7 mol.% CaO; At least 7 mol.% Li₂O; and Less than 4 mol.% Na2O.

2. The glass according to any of the preceding claims, comprising 58-64 mol.% Si2O.

3. The glass according to any of the preceding claims, comprising 9.5-14 mol.% Al2O3.

4. The glass according to any of the preceding claims, comprising 8-30 mol.% MgO.

5. The glass according to any of the preceding claims, comprising 7-20 mol.% CaO.

6. The glass according to any of the preceding claims, comprising 7-20 mol.% Li2O.

7. The glass according to any of the preceding claims, comprising >0-1 mol.% SnO2.

8. The glass according to any of the preceding claims, comprising less than 2 mol.% Na2O.

9. The glass according to any of the preceding claims, comprising: 58-63 mol.% SiO2; mol.% Al2O3; 8-15 mol.% MgO; 7-15 mol.% CaO; 7-15 mol.% Li₂O; and Less than 1 mol.% Li2O.

10. The glass according to any of the preceding claims, comprising at least one of the following: R2O / Al2O3; The RO / Al2O3 ratio must be at least 1.

4. The ratio of (RO + R2O) / Al2O3 is at least 2; The amounts are expressed in mol.%; R2O is the total amount of Li2O, Na2O, K2O, Rb2O and Cs2O in the glass, and RO is the total amount of MgO, CaO, SrO and BaO in the glass.

11. The glass according to any of the preceding claims, wherein the glass is substantially free of at least one of ZrO2, Y2O3, La2O3, Na2O, K2O, P2O5, SrO and B2O3.

12. The glass according to any of the preceding claims, having a Young's modulus of 84-106 GPa.

13. The glass according to any of the preceding claims, comprising a liquidus temperature of 1000-1300°C.

14. The glass according to any of the preceding claims, having a liquidus viscosity of 800-1900 poise.

15. A method for ion-exchanging a glass substrate, the method comprising: The glass substrate is subjected to ion exchange in a first molten salt bath to form a glass-based article. The glass substrate includes a compressive stress layer extending from the surface of the glass substrate to a certain compression depth, the glass substrate includes a central tension region, and the glass substrate comprises glass according to any of the preceding claims.

16. The method of claim 15, wherein the first molten salt bath comprises NaNO3.

17. The method according to claim 15 or 16, wherein the first molten salt bath comprises NaNO3 and LiNO3.

18. The method of claim 16 or 16, wherein the first molten salt bath comprises 100 wt.% NaNO3.

19. The method according to any one of claims 15 to 17, wherein the first molten salt bath comprises KNO3.

20. The method according to any one of claims 15 to 19, wherein the first molten salt bath is at a temperature of 400-550°C.

21. The method according to any one of claims 15 to 20, wherein the ion exchange lasts for a period of 1 to 48 hours.

22. The method according to any one of claims 15 to 21, wherein the ion exchange further comprises a second molten salt bath following the first molten salt bath.

23. The method of claim 22, wherein the temperature of the second molten salt bath is lower than the temperature of the first molten salt bath.

24. The method according to claim 22 or 23, wherein the second molten salt bath comprises NaNO3, KNO3, or a combination thereof.

25. A glass-based article comprising: A compressive stress layer, the compressive stress layer extending from the surface of the glass substrate to a certain compression depth; Central tension region; and The composition located at the center of the glass-based article, the composition comprising: 57-68 mol.% SiO2; mol.% Al2O3; At least 8 mol.% MgO; At least 7 mol.% CaO; At least 7 mol.% Li₂O; and Less than 4 mol.% Na2O.

26. The glass-based article of claim 25, wherein the compressive stress layer contains a compressive stress of at least 155 MPa at a compression depth of at least 10 micrometers.

27. The glass-based article of claim 25 or 26, wherein the compressive stress layer contains a compressive stress of at least 155 MPa at all compression depths from 0 to 45 micrometers.

28. The glass-based article according to any one of claims 25 to 27, wherein the compressive stress layer contains a maximum surface compressive stress of at least 800 MPa.

29. The glass-based article according to any one of claims 25 to 28, wherein the compressive stress layer comprises compressive stress peaks extending from the surface of the glass-based article to a certain compressive stress peak depth, and the compressive stress peak depth is 2-10 micrometers.

30. The glass-based article according to any one of claims 25 to 29, wherein the central tension region comprises a maximum central tension of 50-200 MPa.

31. The glass-based article according to any one of claims 25 to 30, wherein the compression depth is 50-130 micrometers.

32. The glass-based article according to any one of claims 25 to 31, wherein the compression depth is 0.05t-0.25t, where t is the thickness of the glass-based article.

33. The glass-based article according to any one of claims 25 to 32, wherein the thickness t of the glass-based article is 0.2-2 mm.

34. The glass-based article according to any one of claims 25 to 33, wherein the composition at the center of the glass-based article comprises 58-64 mol.% Si2O.

35. The glass-based article according to any one of claims 25 to 34, wherein the composition at the center of the glass-based article comprises 9.5-14 mol.% Al2O3.

36. The glass-based article according to any one of claims 25 to 35, wherein the composition at the center of the glass-based article comprises 8-30 mol.% MgO.

37. The glass-based article according to any one of claims 25 to 36, wherein the composition at the center of the glass-based article comprises 7-20 mol.% CaO.

38. The glass-based article according to any one of claims 25 to 37, wherein the composition at the center of the glass-based article comprises 7-20 mol.% Li2O.

39. The glass-based article according to any one of claims 25 to 38, wherein the composition at the center of the glass-based article comprises >0-1 mol.% SnO2.

40. The glass-based article according to any one of claims 25 to 39, wherein the composition at the center of the glass-based article contains less than 2 mol.% Na2O.

41. The glass-based article according to any one of claims 25 to 40, wherein the composition at the center of the glass-based article comprises: 58-63 mol.% SiO2; mol.% Al2O3; 8-15 mol.% MgO; 7-15 mol.% CaO; 7-15 mol.% Li₂O; and Less than 1 mol.% Na2O.

42. The glass-based article according to any one of claims 25 to 41, wherein the composition at the center of the glass-based article comprises at least one of the following: R2O / Al2O3; The RO / Al2O3 ratio must be at least 1.

4. The ratio of (RO + R2O) / Al2O3 is at least 2; The amounts are expressed in mol.%; R2O is the total amount of Li2O, Na2O, K2O, Rb2O and Cs2O in the glass, and RO is the total amount of MgO, CaO, SrO and BaO in the glass.

43. The glass-based article according to any one of claims 25 to 42, wherein the composition at the center of the glass-based article comprises substantially free of at least one of ZrO2, Y2O3, La2O3, Na2O, K2O, P2O5, SrO and B2O3.

44. The glass-based article according to any one of claims 25 to 43, wherein the glass having the same composition and microstructure as the composition at the center of the glass-based article has a Young's modulus of 84-106 GPa.

45. The glass-based article according to any one of claims 25 to 44, wherein the glass having the same composition and microstructure as the composition at the center of the glass-based article has a liquidus temperature of 1000-1300°C.

46. ​​The glass-based article according to any one of claims 25 to 45, wherein the glass having the same composition and microstructure as the composition at the center of the glass-based article has a liquidus viscosity of 800-1900 poise.

47. The glass-based article according to any one of claims 25 to 46, wherein the compressive stress layer comprises compressive stress, and the integral of the compressive stress from 6 micrometers to the compression depth is at least 10.

5.

48. A consumer electronics product comprising: The housing has a front surface, a rear surface, and side surfaces; Electrical components, at least partially disposed within the housing, the electrical components including at least a controller, a memory, and a display, the display being disposed on or adjacent to the front surface of the housing; as well as A cover plate, which is disposed above the display; At least a portion of at least one of the outer casing and the cover substrate comprises a glass-based article according to any one of claims 25 to 47.

Citation Information

Patent Citations

  • Glasses and glass ceramics including a metal oxide concentration gradient

    US20160102011A1

  • Glasses and glass ceramics including a metal oxide concentration gradient

    US20160102014A1